7q31.2q31.31 deletion downstream of FOXP2 segregating in a family with speech and language disorder - Rieger, Melissa; Krumbiegel, Mandy; Reuter, Miriam; Schützenberger, Anne; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2020)
Chromosomal 7q31 deletions have been described in individuals with variable neurodevelopmental phenotypes including speech and language impairment. These copy number variants usually encompass FOXP2, haploinsufficiency of which represents a widely acknowledged cause for specific speech and language disorders. By chromosomal microarray analysis we identified a 4.7 Mb microdeletion at 7q31.2q31.31 downstream of FOXP2 in three family members presenting with variable speech, language and neurodevelopmental phenotypes. The index individual showed delayed speech development with impaired speech production, reduced language comprehension, and additionally learning difficulties, microcephaly, and attention deficit. His younger sister had delayed speech development with impaired speech production and partially reduced language comprehension. Their mother had attended a school for children with speech and language deficiencies and presented with impaired articulation. The deletion had occurred de novo in the mother, includes 15 protein-coding genes and is located in close proximity to the 3′ end of FOXP2. Though a novel locus at 7q31.2q31.31 associated with mild neurodevelopmental and more prominent speech and language impairment is possible, the close phenotypic overlap with FOXP2-associated speech and language disorder rather suggests a positional effect on FOXP2 expression and function.
CRIS-Team Scopus Importer:2020-09-11
Keywords: 7q; deletion; FOXP2; language; speech

A case of autosomal recessive spinocerebellar ataxia type 18 with a novel mutation in GRID2 - Hetzelt, Katalin; Kraus, Cornelia; Kusnik, Stefan; Thiel, C.; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

A case of severe autosomal recessive spinocerebellar ataxia type 18 with a novel nonsense variant in GRID2 - Hetzelt, Katalin; Kraus, Cornelia; Kusnik, Stefan; Thiel, Christian; Uebe, Steffen; Ekici, Arif Bülent; Trollmann, Regina; Reis, André; Zweier, Christiane (European Journal of Medical Genetics, 2020)
Autosomal-recessive spinocerebellar ataxia type 18 (SCAR18) is a rare neurologic disorder. It is caused by bi-allelic aberrations in the GRID2 gene, encoding an ionotropic glutamate receptor. In total, 20 affected individuals with mainly homozygous/compound heterozygous intragenic deletions/duplications, two different missense variants and one nonsense variant in GRID2 have been reported, so far. SCAR18 is characterized by delayed psychomotor development, intellectual disability, severely impaired gait due to cerebellar ataxia, ocular movement abnormalities, and cerebellar atrophy in brain imaging. By trio exome sequencing, we now identified a novel homozygous nonsense variant (c.568C > T; p.Gln190*) in GRID2 in a four year old female from a consanguineous family who presented with a particularly severe manifestation of SCAR18. The girl was born after an uneventful pregnancy and showed early-onset, profoundly delayed psychomotor development with no achieved psychomotor milestones at age 4 years. Additionally, she presented with severe muscular hypotonia, progressive truncal and appendicular ataxia, binocular vertical nystagmus, central hearing loss and incomplete loss of sight. She was dystrophic, interacted only very little and had behavioral anomalies such as eating hair and bruxism. Brain imaging showed cerebellar hypoplasia, extended cerebrospinal fluid spaces and beginning reduction of cerebral volume. Our findings further delineate the mutational and clinical spectrum of GRID2-associated spinocerebellar ataxia type 18 and indicate that homozygous nonsense variants are possibly associated with the severe end of the SCAR18 phenotypic spectrum.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Ataxia; Autosomal-recessive; Cerebellar hypoplasia; GRID2; Psychomotor development; SCAR18

A complex microcephaly syndrome in a Pakistani family associated with a novel missense mutation in RBBP8 and a heterozygous deletion in NRXN1 - Agha, Zehra; Iqbal, Zafar; Azam, Maleeha; Siddique, Maimoona; Willemsen, Marjolein H.; Kleefstra, Tjitske; Zweier, Christiane; De Leeuw, Nicole; Qamar, Raheel; Van Bokhoven, Hans (Gene, 2014)
We report on a consanguineous Pakistani family with a severe congenital microcephaly syndrome resembling the Seckel syndrome and Jawad syndrome. The affected individuals in this family were born to consanguineous parents of whom the mother presented with mild intellectual disability (ID), epilepsy and diabetes mellitus. The two living affected brothers presented with microcephaly, white matter disease of the brain, hyponychia, dysmorphic facial features with synophrys, epilepsy, diabetes mellitus and ID. Genotyping with a 250K SNP array in both affected brothers revealed an 18 MB homozygous region on chromosome 18 p11.21-q12.1 encompassing the SCKL2 locus of the Seckel and Jawad syndromes. Sequencing of the RBBP8 gene, underlying the Seckel and Jawad syndromes, identified the novel mutation c.919A>G, p.Arg307Gly, segregating in a recessive manner in the family. In addition, in the two affected brothers and their mother we have also found a heterozygous 607kb deletion, encompassing exons 13-19 of NRXN1. Bidirectional sequencing of the coding exons of NRXN1 did not reveal any other mutation on the other allele. It thus appears that the phenotype of the mildly affected mother can be explained by the NRXN1 deletion, whereas the more severe and complex microcephalic phenotype of the two affected brothers is due to the simultaneous deletion in NRXN1 and the homozygous missense mutation affecting RBBP8.
EVALuna2:9226

A de novo microdeletion in NRXN1 in a Dutch patient with mild intellectual disability, microcephaly and gonadal dysgenesis - Agha, Zehra; Iqbal, Zafar; Kleefstra, Tjitske; Zweier, Christiane; Pfundt, Rolph; Qamar, Raheel; Van Bokhoven, Hans; Willemsen, Marjolein H. (Genetics Research, 2015)
This report is regarding a Dutch female with microcephaly, mild intellectual disability (ID), gonadal dysgenesis and dysmorphic facial features with synophrys. Upon genotyping, an 455 kb de novo deletion encompassing the first exon of NRXN1 was found. Bidirectional sequencing of the coding exons of the NRXN1 alpha isoform was subsequently performed to investigate the possibility of a pathogenic mutation on the other allele, but we could not find any other mutation. Previously, many heterozygous mutations as well as microdeletions in NRXN1 were shown to be associated with ID, autism, schizophrenia, and other psychiatric and psychotic disorders. Our results are in agreement with other reports that show that NRXN1 deletions can lead to ID, microcephaly and mild dysmorphic features. However, this is the first report of gonadal dysgenesis being associated with such deletions. It is not clear whether there is a causal relationship between the NRXN1 deletion and gonadal dysgenesis, but it is of interest that the FSHR gene, which encodes the follicle-stimulating hormone receptor causative correlation that is mutated in ovarian dysgenesis, is located proximal to the NRXN1 gene. Given that most of the females carrying NRXN1 deletions have been diagnosed at a prepubertal age, gynecologic screening of female carriers of a NRXN1 deletion is warranted.
EVALuna2:9289

Altered GPM6A/M6 Dosage Impairs Cognition and Causes Phenotypes Responsive to Cholesterol in Human and Drosophila - Gregor, Anne; Kramer, Jamie M.; Van Der Voet, Monique; Schanze, Ina; Uebe, Steffen; Donders, Rogier; Reis, André; Schenck, Annette; Zweier, Christiane (Human Mutation, 2014)
Glycoprotein M6A (GPM6A) is a neuronal transmembrane protein of the PLP/DM20 (proteolipid protein) family that associates with cholesterol-rich lipid rafts and promotes filopodia formation. We identified a de novo duplication of the GPM6A gene in a patient with learning disability and behavioral anomalies. Expression analysis in blood lymphocytes showed increased GPM6A levels. An increase of patient-derived lymphoblastoid cells carrying membrane protrusions supports a functional effect of this duplication. To study the consequences of GPM6A dosage alterations in an intact nervous system, we employed Drosophila melanogaster as a model organism. We found that knockdown of Drosophila M6, the sole member of the PLP family in flies, in the wing, and whole organism causes malformation and lethality, respectively. These phenotypes as well as the protrusions of patient-derived lymphoblastoid cells with increased GPM6A levels can be alleviated by cholesterol supplementation. Notably, overexpression as well as loss of M6 in neurons specifically compromises long-term memory in the courtship conditioning paradigm. Our findings thus indicate a critical role of correct GPM6A/M6 levels for cognitive function and support a role of the GPM6A duplication for the patient's phenotype. Together with other recent findings, this study highlights compromised cholesterol homeostasis as a recurrent feature in cognitive phenotypes.
EVALuna2:9228

Analysis of the expression pattern of the schizophrenia-risk and intellectual disability gene TCF4 in the developing and adult brain suggests a role in development and plasticity of cortical and hippocampal neurons - Jung, Matthias; Häberle, Benjamin; Tschaikowsky, Tristan; Wittmann, Marie-Theres; Balta, Elli-Anna; Stadler, Vivien-Charlott; Zweier, Christiane; Dörfler, Arnd; Gloeckner, Christian Johannes; Lie, Dieter Chichung (Molecular Autism, 2018)
Background: Haploinsufficiency of the class I bHLH transcription factor TCF4 causes Pitt-Hopkins syndrome (PTHS), a severe neurodevelopmental disorder, while common variants in the TCF4 gene have been identified as susceptibility factors for schizophrenia. It remains largely unknown, which brain regions are dependent on TCF4 for their development and function. Methods: We systematically analyzed the expression pattern of TCF4 in the developing and adult mouse brain. We used immunofluorescent staining to identify candidate regions whose development and function depend on TCF4. In addition, we determined TCF4 expression in the developing rhesus monkey brain and in the developing and adult human brain through analysis of transcriptomic datasets and compared the expression pattern between species. Finally, we morphometrically and histologically analyzed selected brain structures in Tcf4-haploinsufficient mice and compared our morphometric findings to neuroanatomical findings in PTHS patients. Results: TCF4 is broadly expressed in cortical and subcortical structures in the developing and adult mouse brain. The TCF4 expression pattern was highly similar between humans, rhesus monkeys, and mice. Moreover, Tcf4 haploinsufficiency in mice replicated structural brain anomalies observed in PTHS patients. Conclusion: Our data suggests that TCF4 is involved in the development and function of multiple brain regions and indicates that its regulation is evolutionary conserved. Moreover, our data validate Tcf4-haploinsufficient mice as a model to study the neurodevelopmental basis of PTHS.
EVALuna:34022

A novel splice variant expands the LAMC3-associated cortical phenotype to frontal only polymicrogyria and adult-onset epilepsy - Kasper, Burkhard; Kraus, Cornelia; Schwarz, Michael; Rösch, Julie; Thiel, Christian; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2020)
Bi-allelic loss-of-function variants in LAMC3, encoding extracellular matrix protein laminin gamma 3, represent a rare cause of occipital polymicrogyria with epilepsy, developmental delay and cognitive impairment. So far, only five families have been reported. We now identified a novel, homozygous splice variant in LAMC3 in an individual with an unusual manifestation of cortical malformation. She presented with polymicrogyria in the frontal but not the occipital lobes, with adult-onset seizures and normal psychomotor development and cognition. Additionally, ictal asystole, requiring implantation of a pacemaker, and nonepileptic seizures occurred. This case expands the spectrum of LAMC3-associated cortical malformation phenotypes to frontal only polymicrogyria and adult-onset of epilepsy.
CRIS-Team Scopus Importer:2020-09-18
Keywords: cortical malformation; epilepsy; LAMC3; polymicrogyria; seizures

Author Correction: CHD3 helicase domain mutations cause a neurodevelopmental syndrome with macrocephaly and impaired speech and language - Blok, Lot Snijders; Rousseau, Justine; Twist, Joanna; Ehresmann, Sophie; Takaku, Motoki; Venselaar, Hanka; Rodan, Lance H.; Nowak, Catherine B.; Douglas, Jessica; Swoboda, Kathryn J.; Steeves, Marcie A.; Sahai, Inderneel; et al. (Nature Communications, 2019)
EVALuna2:206986

Autosomal recessive Noonan syndrome associated with biallelic LZTR1 variants - Johnston, Jennifer J.; Van Der Smagt, Jasper J.; Rosenfeld, Jill A.; Pagnamenta, Alistair T.; Alswaid, Abdulrahman; Baker, Eva H.; Blair, Edward; Borck, Guntram; Brinkmann, Julia; Craigen, William; Vu Chi Dung; Emrick, Lisa; et al. (Genetics in Medicine, 2018)
PurposeTo characterize the molecular genetics of autosomal recessive Noonan syndrome.MethodsFamilies underwent phenotyping for features of Noonan syndrome in children and their parents. Two multiplex families underwent linkage analysis. Exome, genome, or multigene panel sequencing was used to identify variants. The molecular consequences of observed splice variants were evaluated by reverse-transcription polymerase chain reaction.ResultsTwelve families with a total of 23 affected children with features of Noonan syndrome were evaluated. The phenotypic range included mildly affected patients, but it was lethal in some, with cardiac disease and leukemia. All of the parents were unaffected. Linkage analysis using a recessive model supported a candidate region in chromosome 22q11, which includes LZTR1, previously shown to harbor mutations in patients with Noonan syndrome inherited in a dominant pattern. Sequencing analyses of 21 live-born patients and a stillbirth identified biallelic pathogenic variants in LZTR1, including putative loss-of-function, missense, and canonical and noncanonical splicing variants in the affected children, with heterozygous, clinically unaffected parents and heterozygous or normal genotypes in unaffected siblings.ConclusionThese clinical and genetic data confirm the existence of a form of Noonan syndrome that is inherited in an autosomal recessive pattern and identify biallelic mutations in LZTR1.Genet Med advance online publication, 22 February 2018; doi:10.1038/gim.2017.249.
EVALuna2:34635

BCL11A intellectual developmental disorder: defining the clinical spectrum and genotype-phenotype correlations - Peron, Angela; D’Arco, Felice; Aldinger, Kimberly A.; Smith-Hicks, Constance; Zweier, Christiane; Gradek, Gyri A.; Bradbury, Kimberley; Accogli, Andrea; Andersen, Erica F.; Au, Ping Yee Billie; Battini, Roberta; Beleford, Daniah; et al. (European Journal of Human Genetics, 2024)
An increasing number of individuals with intellectual developmental disorder (IDD) and heterozygous variants in BCL11A are identified, yet our knowledge of manifestations and mutational spectrum is lacking. To address this, we performed detailed analysis of 42 individuals with BCL11A-related IDD (BCL11A-IDD, a.k.a. Dias-Logan syndrome) ascertained through an international collaborative network, and reviewed 35 additional previously reported patients. Analysis of 77 affected individuals identified 60 unique disease-causing variants (30 frameshift, 7 missense, 6 splice-site, 17 stop-gain) and 8 unique BCL11A microdeletions. We define the most prevalent features of BCL11A-IDD: IDD, postnatal-onset microcephaly, hypotonia, behavioral abnormalities, autism spectrum disorder, and persistence of fetal hemoglobin (HbF), and identify autonomic dysregulation as new feature. BCL11A-IDD is distinguished from 2p16 microdeletion syndrome, which has a higher incidence of congenital anomalies. Our results underscore BCL11A as an important transcription factor in human hindbrain development, identifying a previously underrecognized phenotype of a small brainstem with a reduced pons/medulla ratio. Genotype-phenotype correlation revealed an isoform-dependent trend in severity of truncating variants: those affecting all isoforms are associated with higher frequency of hypotonia, and those affecting the long (BCL11A-L) and extra-long (-XL) isoforms, sparing the short (-S), are associated with higher frequency of postnatal microcephaly. With the largest international cohort to date, this study highlights persistence of fetal hemoglobin as a consistent biomarker and hindbrain abnormalities as a common feature. It contributes significantly to our understanding of BCL11A-IDD through an extensive unbiased multi-center assessment, providing valuable insights for diagnosis, management and counselling, and into BCL11A’s role in brain development.
CRIS-Team Scopus Importer:2024-11-08

Biallelic intragenic deletion in MASP1 in an adult female with 3MC syndrome - Graul-Neumann, Luitgard M.; Mensah, Martin A.; Klopocki, Eva; Uebe, Steffen; Ekici, Arif Bülent; Thiel, Christian; Reis, André; Zweier, Christiane (European Journal of Medical Genetics, 2018)
3MC syndrome is a rare autosomal recessive disorder with characteristic craniofacial dysmorphism and multiple anomalies. It is caused by biallelic mutations in one of three genes, MASP1, COLEC11 and COLEC10, all encoding factors of the lectin complement pathway. In MASP1, either truncating mutations or missense variants in exon 12 encoding the C-terminal serine protease domain specific for isoform MASP-3 are causative. By trio exome sequencing we now identified a novel, homozygous 2kb deletion, partially affecting exon 12 in an adult female with the typical facial gestalt of 3MC syndrome and hearing loss, but without the main feature cleft lip/palate, and without intellectual disability, or short stature. We therefore expand the MASP1 associated mutational and clinical spectrum and describe the development of her clinical presentation over a period of 21 years. As the homozygous deletion in our patient was only found by thorough and visual evaluation of the whole exome sequencing data, such deletions might escape detection in some routine diagnostic workflows and might explain a few of the so far molecularly unconfirmed cases of 3MC syndrome.
EVALuna2:34626

Biallelic SEMA3A defects cause a novel type of syndromic short stature - Hofmann, Kristin; Zweier, Markus; Sticht, Heinrich; Zweier, Christiane; Wittmann, Wolfgang; Hoyer, Juliane; Uebe, Steffen; Van Haeringen, Arie; Thiel, Christian; Ekici, Arif Bülent; Reis, André; Rauch, Anita (American Journal of Medical Genetics Part A, 2013)
Chromosomal microarray testing is commonly used to identify disease causing de novo copy number variants in patients with developmental delay and multiple congenital anomalies. In such a patient we now observed an 150 kb deletion on chromosome 7q21.11 affecting the first exon of the axon guidance molecule gene SEMA3A (sema domain, immunoglobulin domain (Ig), short basic domain, secreted, (semaphorin) 3A). This deletion was inherited from the healthy father, but considering the function of SEMA3A and phenotypic similarity to the knock-out mice, we still assumed a pathogenic relevance and tested for a recessive second defect. Sequencing of SEMA3A in the patient indeed revealed the de novo in-frame mutation p.Phe316_Lys317delinsThrSerSerAsnGlu. Cloning of the mutated allele in combination with two informative SNPs confirmed compound heterozygosity in the patient. While the altered protein structure was predicted to be benign, aberrant splicing resulting in a premature stop codon was proven by RT-PCR to occur in about half of the transcripts from this allele. Expression profiling in human fetal and adult cDNA panels, confirmed a high expression of SEMA3A in all brain regions as well as in adult and fetal heart and fetal skeletal muscle. Normal intellectual development in the patient was surprising but may be explained by the remaining 20% of SEMA3A expression level demonstrated by quantitative RT-PCR. We therefore report a novel autosomal recessive syndrome characterized by postnatal short stature with relative macrocephaly, camptodactyly, septal heart defect and several minor anomalies caused by biallelic mutations in SEMA3A.
EVALuna2:9194

Central nervous system anomalies in two females with Borjeson-Forssman-Lehmann syndrome - Kasper, Burkhard; Dörfler, Arnd; Di Donato, Nataliya; Kasper, Ekkehard M.; Wieczorek, Dagmar; Hoyer, Juliane; Zweier, Christiane (Epilepsy and Behavior, 2017)
Borjeson-Forssman-Lehmann syndrome (BFLS) is a rare disorder caused by mutations in the PHF6 gene. It manifests as syndromic X-linked recessive intellectual disability (ID) in males and as sporadic ID due to de novo mutations in females. Clinical features include variable ID and a range of somatic manifestations constituting a distinct phenotype in both males and females, respectively, including seizures in a few. Central nervous system (CNS) imaging data are largely unavailable for BFLS. Here we report on CNS MRI findings from two female individuals with BFLS due to a de novo duplication in PHF6 who presented with typical BFLS and epilepsy. Brain findings encompass an intriguing combination of structural abnormalities including a simplified gyral pattern and aspects resembling subcortical band heterotopia as signs of malformation of cortical development (MCD). This finding is of note, since PHF6 has been suggested to play pivotal roles in CNS development including neuronal migration.
EVALuna2:9368

CERT1 mutations perturb human development by disrupting sphingolipid homeostasis - Gehin, Charlotte; Lone, Museer A.; Lee, Winston; Capolupo, Laura; Ho, Sylvia; Adeyemi, Adekemi M.; Gerkes, Erica H.; Stegmann, Alexander Pa; López-Martín, Estrella; Bermejo-Sánchez, Eva; Martínez-Delgado, Beatriz; Zweier, Christiane; et al. (Journal of Clinical Investigation, 2023)
Neural differentiation, synaptic transmission, and action potential propagation depend on membrane sphingolipids, whose metabolism is tightly regulated. Mutations in the ceramide transporter CERT (CERT1), which is involved in sphingolipid biosynthesis, are associated with intellectual disability, but the pathogenic mechanism remains obscure. Here, we characterize 31 individuals with de novo missense variants in CERT1. Several variants fall into a previously uncharacterized dimeric helical domain that enables CERT homeostatic inactivation, without which sphingolipid production goes unchecked. The clinical severity reflects the degree to which CERT autoregulation is disrupted, and inhibiting CERT pharmacologically corrects morphological and motor abnormalities in a Drosophila model of the disease, which we call ceramide transporter (CerTra) syndrome. These findings uncover a central role for CERT autoregulation in the control of sphingolipid biosynthetic flux, provide unexpected insight into the structural organization of CERT, and suggest a possible therapeutic approach for patients with CerTra syndrome.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Cell Biology; Genetics; Lipid rafts; Neurodevelopment

CHD3 helicase domain mutations cause a neurodevelopmental syndrome with macrocephaly and impaired speech and language - Blok, Lot Snijders; Rousseau, Justine; Twist, Joanna; Ehresmann, Sophie; Takaku, Motoki; Venselaar, Hanka; Rodan, Lance H.; Nowak, Catherine B.; Douglas, Jessica; Swoboda, Kathryn J.; Steeves, Marcie A.; Sahai, Inderneel; et al. (Nature Communications, 2018)
Chromatin remodeling is of crucial importance during brain development. Pathogenic alterations of several chromatin remodeling ATPases have been implicated in neurodevelopmental disorders. We describe an index case with a de novo missense mutation in CHD3, identified during whole genome sequencing of a cohort of children with rare speech disorders. To gain a comprehensive view of features associated with disruption of this gene, we use a genotype-driven approach, collecting and characterizing 35 individuals with de novo CHD3 mutations and overlapping phenotypes. Most mutations cluster within the ATPase/helicase domain of the encoded protein. Modeling their impact on the three-dimensional structure demonstrates disturbance of critical binding and interaction motifs. Experimental assays with six of the identified mutations show that a subset directly affects ATPase activity, and all but one yield alterations in chromatin remodeling. We implicate de novo CHD3 mutations in a syndrome characterized by intellectual disability, macrocephaly, and impaired speech and language.
EVALuna2:34823

CHD3 helicase domain mutations cause a neurodevelopmental syndrome with macrocephaly and impaired speech and language (vol 9, 4619, 2018) - Blok, Lot Snijders; Rousseau, Justine; Twist, Joanna; Ehresmann, Sophie; Takaku, Motoki; Venselaar, Hanka; Rodan, Lance H.; Nowak, Catherine B.; Douglas, Jessica; Swoboda, Kathryn J.; Steeves, Marcie A.; Sahai, Inderneel; et al. (Nature Communications, 2019)
EVALuna2:206977

Chromatin-Remodeling-Factor ARID1B Represses Wnt/?-Catenin Signaling - Vasileiou, Georgia; Ekici, Arif Bülent; Urebe, Steffen; Zweier, Christiane; Hoyer, Juliane; Engels, Hartmut; Behrens, Jürgen; Reis, André; Hadjihannas, Michel (American Journal of Human Genetics, 2015)
The link of chromatin remodeling to both neurodevelopment and cancer has recently been highlighted by the identification of mutations affecting BAF chromatin-remodeling components, such as ARID1B, in individuals with intellectual disability and cancer. However, the underlying molecular mechanism(s) remains unknown. Here, we show that ARID1B is a repressor of Wnt/?-catenin signaling. Through whole-transcriptome analysis, we find that in individuals with intellectual disability and ARID1B loss-of-function mutations, Wnt/?-catenin target genes are upregulated. Using cellular models of low and high Wnt/?-catenin activity, we demonstrate that knockdown of ARID1B activates Wnt/?-catenin target genes and Wnt/?-catenin-dependent transcriptional reporters in a ?-catenin-dependent manner. Reciprocally, forced expression of ARID1B inhibits Wnt/?-catenin signaling downstream of the ?-catenin destruction complex. Both endogenous and exogenous ARID1B associate with ?-catenin and repress Wnt/?-catenin-mediated transcription through the BAF core subunit BRG1. Accordingly, mutations in ARID1B leading to partial or complete deletion of its BRG1-binding domain, as is often observed in intellectual disability and cancers, compromise association with ?-catenin, and the resultant ARID1B mutant proteins fail to suppress Wnt/?-catenin signaling. Finally, knockdown of ARID1B in mouse neuroblastoma cells leads to neurite outgrowth through ?-catenin. The data suggest that aberrations in chromatin-remodeling factors, such as ARID1B, might contribute to neurodevelopmental abnormalities and cancer through deregulation of developmental and oncogenic pathways, such as the Wnt/?-catenin signaling pathway.
EVALuna2:9258

Clinical and molecular description of 19 patients with GATAD2B-Associated Neurodevelopmental Disorder (GAND) - Vera, Gabriella; Sorlin, Arthur; Delplancq, Geoffroy; Lecoquierre, François; Brasseur-Daudruy, Marie; Petit, Florence; Smol, Thomas; Ziegler, Alban; Bonneau, Dominique; Colin, Estelle; Mercier, Sandra; Cogné, Benjamin; et al. (European Journal of Medical Genetics, 2020)
De novo pathogenic variants in the GATAD2B gene have been associated with a syndromic neurodevelopmental disorder (GAND) characterized by severe intellectual disability (ID), impaired speech, childhood hypotonia, and dysmorphic features. Since its first description in 2013, nine patients have been reported in case reports and a series of 50 patients was recently published, which is consistent with the relative frequency of GATAD2B pathogenic variants in public databases. We report the detailed phenotype of 19 patients from various ethnic backgrounds with confirmed pathogenic GATAD2B variants including intragenic deletions. All individuals presented developmental delay with a median age of 2.5 years for independent walking and of 3 years for first spoken words. GATAD2B variant carriers showed very little subsequent speech progress, two patients over 30 years of age remaining non-verbal. ID was mostly moderate to severe, with one profound and one mild case, which shows a wider spectrum of disease severity than previously reported. We confirm macrocephaly as a major feature in GAND (53%). Most common dysmorphic features included broad forehead, deeply set eyes, hypertelorism, wide nasal base, and pointed chin. Conversely, prenatal abnormalities, non-cerebral malformations, epilepsy, and autistic behavior were uncommon. Other features included feeding difficulties, behavioral abnormalities, and unspecific abnormalities on brain MRI. Improving our knowledge of the clinical phenotype is essential for correct interpretation of the molecular results and accurate patient management.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Developmental delay; GATAD2B; Intellectual disability; Next-generation sequencing

Clinical delineation of the PACS1-related syndrome - Report on 19 patients - Schuurs-Hoeijmakers, Janneke H. M.; Landsverk, Megan L.; Foulds, Nicola; Kukolich, Mary K.; Gavrilova, Ralitza H.; Greville-Heygate, Stephanie; Hanson-Kahn, Andrea; Bernstein, Jonathan A.; Glass, Jennifer; Chitayat, David; Burrow, Thomas A.; Husami, Ammar; et al. (American Journal of Medical Genetics Part A, 2016)
We report on 19 individuals with a recurrent de novo c.607C>T mutation in PACS1. This specific mutation gives rise to a recognizable intellectual disability syndrome. There is a distinctive facial appearance (19/19), characterized by full and arched eyebrows, hypertelorism with downslanting palpebral fissures, long eye lashes, ptosis, low set and simple ears, bulbous nasal tip, wide mouth with downturned corners and a thin upper lip with an unusual "wavy" profile, flat philtrum, and diastema of the teeth. Intellectual disability, ranging from mild to moderate, was present in all. Hypotonia is common in infancy (8/19). Seizures are frequent (12/19) and respond well to anticonvulsive medication. Structural malformations are common, including heart (10/19), brain (12/16), eye (10/19), kidney (3/19), and cryptorchidism (6/12 males). Feeding dysfunction is presenting in infancy with failure to thrive (5/19), gastroesophageal reflux (6/19), and gastrostomy tube placement (4/19). There is persistence of oral motor dysfunction. We provide suggestions for clinical work-up and management and hope that the present study will facilitate clinical recognition of further cases.
EVALuna2:9319

Clinical relevance of systematic phenotyping and exome sequencing in patients with short stature - Hauer, Nadine; Popp, Bernt; Schoeller, Eva; Schuhmann, Sarah; Heath, Karen E.; Hisado-Oliva, Alfonso; Klinger, Patricia; Kraus, Cornelia; Trautmann, Udo; Zenker, Martin; Zweier, Christiane; Wiesener, Antje; et al. (Genetics in Medicine, 2018)
PurposeShort stature is a common condition of great concern to patients and their families. Mostly genetic in origin, the underlying cause often remains elusive due to clinical and genetic heterogeneity.MethodsWe systematically phenotyped 565 patients where common nongenetic causes of short stature were excluded, selected 200 representative patients for whole-exome sequencing, and analyzed the identified variants for pathogenicity and the affected genes regarding their functional relevance for growth.ResultsBy standard targeted diagnostic and phenotype assessment, we identified a known disease cause in only 13.6% of the 565 patients. Whole-exome sequencing in 200 patients identified additional mutations in known short-stature genes in 16.5% of these patients who manifested only part of the symptomatology. In 15.5% of the 200 patients our findings were of significant clinical relevance. Heterozygous carriers of recessive skeletal dysplasia alleles represented 3.5% of the cases.ConclusionA combined approach of systematic phenotyping, targeted genetic testing, and whole-exome sequencing allows the identification of the underlying cause of short stature in at least 33% of cases, enabling physicians to improve diagnosis, treatment, and genetic counseling. Exome sequencing significantly increases the diagnostic yield and consequently care in patients with short stature.
EVALuna2:34628

Clinical spectrum of females with HCCS mutation: from no clinical signs to a neonatal lethal form of the microphthalmia with linear skin defects (MLS) syndrome - Van Rahden, Vanessa A.; Rau, Isabella; Fuchs, Sigrid; Kosyna, Friederike K.; De Almeida, Hiram Larangeira; Fryssira, Helen; Isidor, Bertrand; Jauch, Anna; Joubert, Madeleine; Lachmeijer, Augusta M. A.; Zweier, Christiane; Moog, Ute; et al. (Orphanet Journal of Rare Diseases, 2014)
Segmental Xp22.2 monosomy or a heterozygous HCCS mutation is associated with the microphthalmia with linear skin defects (MLS) or MIDAS (microphthalmia, dermal aplasia, and sclerocornea) syndrome, an X-linked disorder with male lethality. HCCS encodes the holocytochrome c-type synthase involved in mitochondrial oxidative phosphorylation (OXPHOS) and programmed cell death.We characterized the X-chromosomal abnormality encompassing HCCS or an intragenic mutation in this gene in six new female patients with an MLS phenotype by cytogenetic analysis, fluorescence in situ hybridization, sequencing, and quantitative real-time PCR. The X chromosome inactivation (XCI) pattern was determined and clinical data of the patients were reviewed.Two terminal Xp deletions of >= 11.2 Mb, two submicroscopic copy number losses, one of 850 kb and one of >= 3 Mb, all covering HCCS, 1 nonsense, and one mosaic 2-bp deletion in HCCS are reported. All females had a completely (>98:2) or slightly skewed (82:18) XCI pattern. The most consistent clinical features were microphthalmia/anophthalmia and sclerocornea/corneal opacity in all patients and congenital linear skin defects in 4/6. Additional manifestations included various ocular anomalies, cardiac defects, brain imaging abnormalities, microcephaly, postnatal growth retardation, and facial dysmorphism. However, no obvious clinical sign was observed in three female carriers who were relatives of one patient.Our findings showed a wide phenotypic spectrum ranging from asymptomatic females with an HCCS mutation to patients with a neonatal lethal MLS form. Somatic mosaicism and the different ability of embryonic cells to cope with an OXPHOS defect and/or enhanced cell death upon HCCS deficiency likely underlie the great variability in phenotypes.
EVALuna2:9233

CLP1 founder mutation links tRNA splicing and maturation to cerebellar development and neurodegeneration - Schaffer, Ashleigh E.; Eggens, Veerle R. C.; Caglayan, Ahmet Okay; Reuter, Miriam; Scott, Eric; Coufal, Nicole G.; Silhavy, Jennifer L.; Xue, Yuanchao; Kayserili, Hulya; Yasuno, Katsuhito; Rosti, Rasim Ozgur; Abdellateef, Mostafa; et al. (Cell, 2014)
Neurodegenerative diseases can occur so early as to affect neurodevelopment. From a cohort of more than 2,000 consanguineous families with childhood neurological disease, we identified a founder mutation in four independent pedigrees in cleavage and polyadenylation factor I subunit 1 (CLP1). CLP1 is a multifunctional kinase implicated in tRNA, mRNA, and siRNA maturation. Kinase activity of the CLP1 mutant protein was defective, and the tRNA endonuclease complex (TSEN) was destabilized, resulting in impaired pre-tRNA cleavage. Germline clp1 null zebrafish showed cerebellar neurodegeneration that was rescued by wild-type, but not mutant, human CLP1 expression. Patient-derived induced neurons displayed both depletion of mature tRNAs and accumulation of unspliced pre-tRNAs. Transfection of partially processed tRNA fragments into patient cells exacerbated an oxidative stress-induced reduction in cell survival. Our data link tRNA maturation to neuronal development and neurodegeneration through defective CLP1 function in humans.
EVALuna2:9222

Correction: Expanded phenotypic spectrum of neurodevelopmental and neurodegenerative disorder Bryant-Li-Bhoj syndrome with 38 additional individuals (European Journal of Human Genetics, (2024), 32, 8, (928-937), 10.1038/s41431-024-01610-1) - Layo-Carris, Dana E.; Lubin, Emily E.; Sangree, Annabel K.; Clark, Kelly J.; Durham, Emily L.; Gonzalez, Elizabeth M.; Smith, Sarina; Angireddy, Rajesh; Wang, Xiao Min; Weiss, Erin; Toutain, Annick; Mendoza-Londono, Roberto; et al. (European Journal of Human Genetics, 2024)
An author was not named. The missing author is: “Annick Toutain” Her affiliation is: 27 Service de Génétique, CHU de Tours, Tours, France. 28 UMR1253, iBrain, Inserm, University of Tours, Tours, France.
CRIS-Team Scopus Importer:2024-08-09

CTCF variants in 31 individuals with a variable neurodevelopmental disorder broaden the mutational and clinical spectrum - Konrad, Enrico; Nardini, N.; Blyth, M.; Prescott, K.; Bouman, A. M.; Brilstra, E. H.; Caliebe, A.; Ibitoye, R.; Chang, V. Y.; Gupta, A.; Le Guyader, G.; Jamra, R. A.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2021-10-18

CTCF variants in 39 individuals with a variable neurodevelopmental disorder broaden the mutational and clinical spectrum - Konrad, Enrico; Nardini, Niels; Caliebe, Almuth; Nagel, Inga; Young, Dana; Horvath, Gabriella; Santoro, Stephanie L.; Shuss, Christine; Ziegler, Alban; Bonneau, Dominique; Kempers, Marlies; Pfundt, Rolph; et al. (Genetics in Medicine, 2019)
Purpose: Pathogenic variants in the chromatin organizer CTCF were previously reported in seven individuals with a neurodevelopmental disorder (NDD). Methods: Through international collaboration we collected data from 39 subjects with variants in CTCF. We performed transcriptome analysis on RNA from blood samples and utilized Drosophila melanogaster to investigate the impact of Ctcf dosage alteration on nervous system development and function. Results: The individuals in our cohort carried 2 deletions, 8 likely gene-disruptive, 2 splice-site, and 20 different missense variants, most of them de novo. Two cases were familial. The associated phenotype was of variable severity extending from mild developmental delay or normal IQ to severe intellectual disability. Feeding difficulties and behavioral abnormalities were common, and variable other findings including growth restriction and cardiac defects were observed. RNA-sequencing in five individuals identified 3828 deregulated genes enriched for known NDD genes and biological processes such as transcriptional regulation. Ctcf dosage alteration in Drosophila resulted in impaired gross neurological functioning and learning and memory deficits. Conclusion: We significantly broaden the mutational and clinical spectrum of CTCF-associated NDDs. Our data shed light onto the functional role of CTCF by identifying deregulated genes and show that Ctcf alterations result in nervous system defects in Drosophila.
Keywords: chromatin organization; CTCF; Drosophila melanogaster; intellectual disability; neurodevelopmental disorders

DDX3X mutations in two girls with a phenotype overlapping Toriello-Carey syndrome - Dikow, Nicola; Granzow, Martin; Graul-Neumann, Luitgard M.; Karch, Stephanie; Hinderhofer, Katrin; Paramasivam, Nagarajan; Behl, Laura-Jane; Kaufmann, Lilian; Fischer, Christine; Evers, Christina; Schlesner, Matthias; Eils, Roland; et al. (American Journal of Medical Genetics Part A, 2017)
Recently, de novo heterozygous variants in DDX3X have been reported in about 1.5% of 2659 females with previously unexplained intellectual disability (ID). We report on the identification of DDX3X variants in two unrelated girls with clinical features of Toriello-Carey Syndrome (T-CS). In patient 1, the recurrent variant c.1703C>T; p.(P568L) was identified when reconsidering X-linked de novo heterozygous variants in exome sequencing data. In patient 2, the DDX3X variant c.1600C>G; p.(R534G) was also detected by exome sequencing. Based on these data, de novo heterozygous DDX3X variants should be considered not only in females with unexplained ID, but also in individuals with a clinical diagnosis of T-CS.
EVALuna2:9360

Deletion 7q31.2q31.31 segregating in a family with speech and language deficiencies - Rieger, Melissa; Krumbiegel, Mandy; Reuter, Miriam; Schützenberger, Anne; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Delineating the clinical spectrum due to heterozygous TRAF7 missense mutations: A series of 38 cases - Amiel, J.; Mishra, K.; Castilla, L.; Selmer, K. K.; Barak, T.; Yang, S.; Blanco-Sanchez, B.; Reijnders, M.; Houge, G.; Cox, H.; Kingston, H.; Clayton-Smith, J.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Delineation of the clinical phenotype caused by de novo CLTC variants - Sa, M. J. Nabais; Venselaar, H.; Wiel, L.; Trimouille, A.; Lasseaux, E.; Naudion, S.; Lacombe, D.; Piton, A.; Vincent-Delorme, C.; Zweier, Christiane; Wiesmann da Silva Reis, André; Trollmann, Regina; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

De novo and inherited variants in ZNF292 underlie a neurodevelopmental disorder with features of autism spectrum disorder - Mirzaa, Ghayda M.; Chong, Jessica X.; Piton, Amélie; Popp, Bernt; Foss, Kimberly; Guo, Hui; Harripaul, Ricardo; Xia, Kun; Scheck, Joshua; Aldinger, Kimberly A.; Sajan, Samin A.; Tang, Sha; et al. (Genetics in Medicine, 2019)
Purpose: Intellectual disability (ID) and autism spectrum disorder (ASD) are genetically heterogeneous neurodevelopmental disorders. We sought to delineate the clinical, molecular, and neuroimaging spectrum of a novel neurodevelopmental disorder caused by variants in the zinc finger protein 292 gene (ZNF292). Methods: We ascertained a cohort of 28 families with ID due to putatively pathogenic ZNF292 variants that were identified via targeted and exome sequencing. Available data were analyzed to characterize the canonical phenotype and examine genotype–phenotype relationships. Results: Probands presented with ID as well as a spectrum of neurodevelopmental features including ASD, among others. All ZNF292 variants were de novo, except in one family with dominant inheritance. ZNF292 encodes a highly conserved zinc finger protein that acts as a transcription factor and is highly expressed in the developing human brain supporting its critical role in neurodevelopment. Conclusion: De novo and dominantly inherited variants in ZNF292 are associated with a range of neurodevelopmental features including ID and ASD. The clinical spectrum is broad, and most individuals present with mild to moderate ID with or without other syndromic features. Our results suggest that variants in ZNF292 are likely a recurrent cause of a neurodevelopmental disorder manifesting as ID with or without ASD.
CRIS-Team Scopus Importer:2019-11-26
Keywords: autism spectrum disorders; exome sequencing; intellectual disability; next-generation sequencing; ZNF292

De novo CLTC variants are associated with a variable phenotype from mild to severe intellectual disability, microcephaly, hypoplasia of the corpus callosum, and epilepsy - Nabais Sá, Maria J.; Venselaar, Hanka; Wiel, Laurens; Trimouille, Aurélien; Lasseaux, Eulalie; Naudion, Sophie; Lacombe, Didier; Piton, Amélie; Vincent-Delorme, Catherine; Zweier, Christiane; Reis, André; Trollmann, Regina; et al. (Genetics in Medicine, 2019)
Purpose: To delineate the genotype–phenotype correlation in individuals with likely pathogenic variants in the CLTC gene. Methods: We describe 13 individuals with de novo CLTC variants. Causality of variants was determined by using the tolerance landscape of CLTC and computer-assisted molecular modeling where applicable. Phenotypic abnormalities observed in the individuals identified with missense and in-frame variants were compared with those with nonsense or frameshift variants in CLTC. Results: All de novo variants were judged to be causal. Combining our data with that of 14 previously reported affected individuals (n = 27), all had intellectual disability (ID), ranging from mild to moderate/severe, with or without additional neurologic, behavioral, craniofacial, ophthalmologic, and gastrointestinal features. Microcephaly, hypoplasia of the corpus callosum, and epilepsy were more frequently observed in individuals with missense and in-frame variants than in those with nonsense and frameshift variants. However, this difference was not significant. Conclusions: The wide phenotypic variability associated with likely pathogenic CLTC variants seems to be associated with allelic heterogeneity. The detailed clinical characterization of a larger cohort of individuals with pathogenic CLTC variants is warranted to support the hypothesis that missense and in-frame variants exert a dominant-negative effect, whereas the nonsense and frameshift variants would result in haploinsufficiency.
CRIS-Team Scopus Importer:2019-12-10
Keywords: CLTC; intellectual disability; neurodevelopmental disorder

De novo coding variants in the AGO1 gene cause a neurodevelopmental disorder with intellectual disability - Schalk, Audrey; Cousin, Margot A.; Challman, Thomas D.; Wain, Karen E.; Powis, Zoe; Minks, Kelly; Trimouille, Aurelien; Lasseaux, Eulalie; Lacombre, Didier; Angelini, Chloe; Michaud, Vincent; Van-Gils, Julien; et al. (Journal of Medical Genetics, 2021)
Background High-impact pathogenic variants in more than a thousand genes are involved in Mendelian forms of neurodevelopmental disorders (NDD). Methods This study describes the molecular and clinical characterisation of 28 probands with NDD harbouring heterozygous AGO1 coding variants, occurring de novo for all those whose transmission could have been verified (26/28). Results A total of 15 unique variants leading to amino acid changes or deletions were identified: 12 missense variants, two in-frame deletions of one codon, and one canonical splice variant leading to a deletion of two amino acid residues. Recurrently identified variants were present in several unrelated individuals: p.(Phe180del), p.(Leu190Pro), p.(Leu190Arg), p.(Gly199Ser), p.(Val254Ile) and p.(Glu376del). AGO1 encodes the Argonaute 1 protein, which functions in gene-silencing pathways mediated by small non-coding RNAs. Three-dimensional protein structure predictions suggest that these variants might alter the flexibility of the AGO1 linker domains, which likely would impair its function in mRNA processing. Affected individuals present with intellectual disability of varying severity, as well as speech and motor delay, autistic behaviour and additional behavioural manifestations. Conclusion Our study establishes that de novo coding variants in AGO1 are involved in a novel monogenic form of NDD, highly similar to the recently reported AGO2-related NDD.
CRIS-Team WoS Importer:2021-12-24

De novo missense variants in FBXO11 alter its protein expression and subcellular localization - Gregor, Anne; Meerbrei, Tanja; Gerstner, Thorsten; Toutain, Annick; Lynch, Sally Ann; Stals, Karen; Maxton, Caroline; Lemke, Johannes R.; Bernat, John A.; Bombei, Hannah M.; Foulds, Nicola; Hunt, David; et al. (Human Molecular Genetics, 2022)
Recently, others and we identified de novo FBXO11 (F-Box only protein 11) variants as causative for a variable neurodevelopmental disorder (NDD). We now assembled clinical and mutational information on 23 additional individuals. The phenotypic spectrum remains highly variable, with developmental delay and/or intellectual disability as the core feature and behavioral anomalies, hypotonia and various facial dysmorphism as frequent aspects. The mutational spectrum includes intragenic deletions, likely gene disrupting and missense variants distributed across the protein. To further characterize the functional consequences of FBXO11 missense variants, we analyzed their effects on protein expression and localization by overexpression of 17 different mutant constructs in HEK293 and HeLa cells. We found that the majority of missense variants resulted in subcellular mislocalization and/or reduced FBXO11 protein expression levels. For instance, variants located in the nuclear localization signal and the N-terminal F-Box domain lead to altered subcellular localization with exclusion from the nucleus or the formation of cytoplasmic aggregates and to reduced protein levels in western blot. In contrast, variants localized in the C-terminal Zn-finger UBR domain lead to an accumulation in the cytoplasm without alteration of protein levels. Together with the mutational data, our functional results suggest that most missense variants likely lead to a loss of the original FBXO11 function and thereby highlight haploinsufficiency as the most likely disease mechanism for FBXO11-associated NDDs.
CRIS-Team Scopus Importer:2022-03-04

De novo missense variants in RHOBTB2 cause a developmental and epileptic encephalopathy in humans, and altered levels cause neurological defects in Drosophila - Straub, Jonas; Konrad, Enrico; Grüner, Johanna; Toutain, A.; Bok, L. A.; Cho, M. T.; Crawford, H. P.; Dubbs, H.; Douglas, G.; Jobling, R.; Johnson, D.; Krock, B.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

De novo mutations in the genome organizer CTCF cause intellectual disability - Gregor, Anne; Oti, Martin; Kouwenhoven, Evelyn N.; Hoyer, Juliane; Sticht, Heinrich; Ekici, Arif Bülent; Kjaergaard, Susanne; Rauch, Anita; Stunnenberg, Hendrik G.; Uebe, Steffen; Vasileiou, Georgia; Reis, André; et al. (American Journal of Human Genetics, 2013)
An increasing number of genes involved in chromatin structure and epigenetic regulation has been implicated in a variety of developmental disorders, often including intellectual disability. By trio exome sequencing and subsequent mutational screening we now identified two de novo frameshift mutations and one de novo missense mutation in CTCF in individuals with intellectual disability, microcephaly, and growth retardation. Furthermore, an individual with a larger deletion including CTCF was identified. CTCF (CCCTC-binding factor) is one of the most important chromatin organizers in vertebrates and is involved in various chromatin regulation processes such as higher order of chromatin organization, enhancer function, and maintenance of three-dimensional chromatin structure. Transcriptome analyses in all three individuals with point mutations revealed deregulation of genes involved in signal transduction and emphasized the role of CTCF in enhancer-driven expression of genes. Our findings indicate that haploinsufficiency of CTCF affects genomic interaction of enhancers and their regulated gene promoters that drive developmental processes and cognition.
EVALuna2:9184

De novo variants in MED12 cause X-linked syndromic neurodevelopmental disorders in 18 females - Polla, D. L.; Bhoj, E. J.; Verheij, J. B.G.M.; Wassink-Ruiter, J. S.Klein; Reis, André; Deshpande, C.; Gregor, Anne; Hill-Karfe, K.; Silfhout, A. T.Vulto van; Pfundt, R.; Bongers, E. M.H.F.; Hakonarson, H.; et al. (Genetics in Medicine, 2020)
Purpose: MED12 is a subunit of the Mediator multiprotein complex with a central role in RNA polymerase II transcription and regulation of cell growth, development, and differentiation. This might underlie the variable phenotypes in males carrying missense variants in MED12, including X-linked recessive Ohdo, Lujan, and FG syndromes. Methods: By international matchmaking we assembled variant and clinical data on 18 females presenting with variable neurodevelopmental disorders (NDDs) and harboring de novo variants in MED12. Results: Five nonsense variants clustered in the C-terminal region, two splice variants were found in the same exon 8 splice acceptor site, and 11 missense variants were distributed over the gene/protein. Protein truncating variants were associated with a severe, syndromic phenotype consisting of intellectual disability (ID), facial dysmorphism, short stature, skeletal abnormalities, feeding difficulties, and variable other abnormalities. De novo missense variants were associated with a less specific, but homogeneous phenotype including severe ID, autistic features, limited speech and variable other anomalies, overlapping both with females with truncating variants as well as males with missense variants. Conclusion: We establish de novo truncating variants in MED12 as causative for a distinct NDD and de novo missense variants as causative for a severe, less specific NDD in females.
CRIS-Team Scopus Importer:2020-12-04

De Novo Variants in the F-Box Protein FBXO11 in 20 Individuals with a Variable Neurodevelopmental Disorder - Gregor, Anne; Sadleir, Lynette G.; Asadollahi, Reza; Azzarello-Burri, Silvia; Battaglia, Agatino; Ousager, Lilian Bomme; Boonsawat, Paranchai; Bruel, Ange-Line; Buchert, Rebecca; Calpena, Eduardo; Cogne, Benjamin; Dallapiccola, Bruno; et al. (American Journal of Human Genetics, 2018)
Next-generation sequencing combined with international data sharing has enormously facilitated identification of new disease-associated genes and mutations. This is particularly true for genetically extremely heterogeneous entities such as neurodevelopmental disorders (NDDs). Through exome sequencing and world-wide collaborations, we identified and assembled 20 individuals with de novo variants in FBXO11. They present with mild to severe developmental delay associated with a range of features including short (4/20) or tall (2/20) stature, obesity (5/20), microcephaly (4/19) or macrocephaly (2/19), behavioral problems (17/20), seizures (5/20), cleft lip or palate or bifid uvula (3/20), and minor skeletal anomalies. FBXO11 encodes a member of the F-Box protein family, constituting a subunit of an E3-ubiquitin ligase complex. This complex is involved in ubiquitination and proteasomal degradation and thus in controlling critical biological processes by regulating protein turnover. The identified de novo aberrations comprise two large deletions, ten likely gene disrupting variants, and eight missense variants distributed throughout FBXO11. Structural modeling for missense variants located in the CASH or the Zinc-finger UBR domains suggests destabilization of the protein. This, in combination with the observed spectrum and localization of identified variants and the lack of apparent genotype-phenotype correlations, is compatible with loss of function or haploinsufficiency as an underlying mechanism. We implicate de novo missense and likely gene disrupting variants in FBXO11 in a neurodevelopmental disorder with variable intellectual disability and various other features.
EVALuna2:34619

Detection rate and re-analysis of exome sequencing data in a cohort of 207 individuals with neurodevelopmental disorders - Hebebrand, Moritz; Thiel, C. T.; Kraus, Cornelia; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Diagnosis and management in Pitt-Hopkins syndrome: First international consensus statement - Zollino, Marcella; Zweier, Christiane; Van Balkom, Ingrid D.; Sweetser, David A.; Alaimo, Joseph; Bijlsma, Emilia K.; Cody, Jannine; Elsea, Sarah H.; Giurgea, Irina; Macchiaiolo, Marina; Smigiel, Robert; Thibert, Ronald L.; et al. (Clinical Genetics, 2019)
Pitt-Hopkins syndrome (PTHS) is a neurodevelopmental disorder characterized by intellectual disability, specific facial features, and marked autonomic nervous system dysfunction, especially with disturbances of regulating respiration and intestinal mobility. It is caused by variants in the transcription factor TCF4. Heterogeneity in the clinical and molecular diagnostic criteria and care practices has prompted a group of international experts to establish guidelines for diagnostics and care. For issues, for which there was limited information available in international literature, we collaborated with national support groups and the participants of a syndrome specific international conference to obtain further information. Here, we discuss the resultant consensus, including the clinical definition of PTHS and a molecular diagnostic pathway. Recommendations for managing particular health problems such as dysregulated respiration are provided. We emphasize the need for integration of care for physical and behavioral issues. The recommendations as presented here will need to be evaluated for improvements to allow for continued optimization of diagnostics and care.
CRIS-Team WoS Importer:2019-04-04

Diagnostics of rare diseases with next generation sequencing—arrived at the patients or rejected? Diagnostik seltener Erkrankungen mit „next generation sequencing“ – angekommen oder abgewehrt? - Abicht, Angela; Neuhann, Teresa; Mehnert, Laura; Rost, Imma; Wiesmann da Silva Reis, André; Zweier, Christiane; Holinski-Feder, Elke (Medizinische Genetik, 2019)
In genetic diagnostics, the path goes from single-gene testing to gene-panel analyses, especially for rare genetic diseases. In July 2016, an amendment to the EBM (Einheitlicher Bewertungsmaßstab, Regulations on Fees for Statutory Health Insurance) introduced the possibility of performing genetic analyses using next-generation sequencing (NGS) on patients with rare diseases. However, the mutation search in a sequence encoding more than 25 kilobases (kb) was subject to approval by the health insurance funds and was further restricted over time by a billing exclusion for a previous analysis of individual genes of less than 25 kb. We report from the diagnostic laboratories of the Bavarian State Association of the BVDH (Berufsverband Deutscher Humangenetiker e. V.) on the experiences we have gained with the application procedures, the objections, the approval rate, the reasons for rejection and the diagnostic outcome in the analysis of large gene panels for various rare disorders. In the survey period of seven quarters, a total of 314 applications were prepared in four diagnostic laboratories to justify an application according to GOP (Gebührenordnungsposition, fee schedule position) 11514, all of which were reviewed by the MDK (Medizinischer Dienst der Krankenkassen; Medical Service to Health Insurance Funds). 71% of the applications were rejected. A total of 95 applications (29%) were approved, but in some cases only after up to five objections. The rejections were based on both socio-medical and formal criteria, whereby in most cases a therapeutic relevance considered to be lacking was used as a socio-medical argument. The approved comprehensive NGS analyses made it possible to make a genetic diagnosis in more than 30% of the patients examined, which was relevant to treatment in two thirds of the cases. In summary, the conditional approval of an NGS analysis according to GOP 11514 and the resulting obstacles hinder the medically necessary and useful diagnostics in the care of patients with rare diseases.
CRIS-Team Scopus Importer:2019-11-19
Keywords: Application procedure “large panel”; Gene panel; Panel diagnostics; Scale of charges position 11514; Uniform assessment benchmark

Diagnostic Yield and Novel Candidate Genes by Exome Sequencing in 152 Consanguineous Families With Neurodevelopmental Disorders - Reuter, Miriam; Tawamie, Hasan; Buchert, Rebecca; Gebril, Ola Hosny; Froukh, Tawfiq; Thiel, Christian; Uebe, Steffen; Ekici, Arif Bülent; Krumbiegel, Mandy; Zweier, Christiane; Hoyer, Juliane; Eberlein, Karolin; et al. (JAMA Psychiatry, 2017)
Autosomal recessive inherited neurodevelopmental disorders are highly heterogeneous, and many, possibly most, of the disease genes are still unknown.To promote the identification of disease genes through confirmation of previously described genes and presentation of novel candidates and provide an overview of the diagnostic yield of exome sequencing in consanguineous families.Autozygosity mapping in families and exome sequencing of index patients were performed in 152 consanguineous families (the parents descended from a same ancestor) with at least 1 offspring with intellectual disability (ID). The study was conducted from July 1, 2008, to June 30, 2015, and data analysis was conducted from July 1, 2015, to August 31, 2016.Of the 152 consanguineous families enrolled, 1 child (in 45 families [29.6%]) or multiple children (107 families [70.4%]) had ID; additional features were present in 140 of the families (92.1%). The mean (SD) age of the children was 10.3 (9.0) years, and 171 of 297 (57.6%) were male. In 109 families (71.7%), potentially protein-disrupting and clinically relevant variants were identified. Of these, a clear clinical genetic diagnosis was made in 56 families (36.8%) owing to 57 (likely) pathogenic variants in 50 genes already established in neurodevelopmental disorders (46 autosomal recessive, 2 X-linked, and 2 de novo) or in 7 previously proposed recessive candidates. In 5 of these families, potentially treatable disorders were diagnosed (mutations in PAH, CBS, MTHFR, CYP27A1, and HIBCH), and in 1 family, 2 disease-causing homozygous variants in different genes were identified. In another 48 families (31.6%), 52 convincing recessive variants in candidate genes that were not previously reported in regard to neurodevelopmental disorders were identified. Of these, 14 were homozygous and truncating in GRM7, STX1A, CCAR2, EEF1D, GALNT2, SLC44A1, LRRIQ3, AMZ2, CLMN, SEC23IP, INIP, NARG2, FAM234B, and TRAP1. The diagnostic yield was higher in individuals with severe ID (35 of 77 [45.5%]), in multiplex families (42 of 107 [39.3%]), in patients with additional features (30 of 70 [42.9%]), and in those with remotely related parents (15 of 34 [44.1%]).Because of the high diagnostic yield of 36.8% and the possibility of identifying treatable diseases or the coexistence of several disease-causing variants, using exome sequencing as a first-line diagnostic approach in consanguineous families with neurodevelopmental disorders is recommended. Furthermore, the literature is enriched with 52 convincing candidate genes that are awaiting confirmation in independent families.
EVALuna2:9388

Dissecting TSC2-mutated renal and hepatic angiomyolipomas in an individual with ARID1B-associated intellectual disability - Popp, Bernt; Agaimy, Abbas; Kraus, Cornelia; Knaup, Karl; Ekici, Arif Bülent; Uebe, Steffen; Reis, André; Wiesener, Michael; Zweier, Christiane (BMC Cancer, 2019)
Background: Several subunits of the SWI/SNF chromatin remodeling complex are implicated in both cancer and neurodevelopmental disorders (NDD). Though there is no clinical evidence for an increased tumor risk in individuals with NDDs due to germline mutations in most of these genes so far, this has been repeatedly proposed and discussed. A young woman with NDD due to a de novo mutation in ARID1B now presented with a large renal (> 19 cm in diameter) and multiple hepatic angiomyolipomas (AMLs) but no other signs of tuberous sclerosis complex. Methods: We analyzed tumor and healthy tissue samples with exome and panel sequencing. Results: Additionally to the previously known, germline ARID1B variant we identified a post-zygotic truncating TSC2 variant in both renal and hepatic AMLs but not in any of the healthy tissues. We did not detect any further, obvious tumor driver events. The identification of a passenger variant in SIPA1L3 in both AMLs points to a common clonal origin. Metastasis of the renal AML into the liver is unlikely on the basis of discordant histopathological features. Our findings therefore point to very low-grade mosaicism for the TSC2 variant, possibly in a yet unknown mesenchymal precursor cell that expanded clonally during tumor development. A possible contribution of the germline ARID1B variant to the tumorigenesis remains unclear but cannot be excluded given the absence of any other evident tumor drivers in the AMLs. Conclusion: This unique case highlights the blurred line between tumor genetics and post-zygotic events that can complicate exact molecular diagnoses in patients with rare manifestations. It also demonstrates the relevance of multiple disorders in a single individual, the challenges of detecting low-grade mosaicisms, and the importance of proper diagnosis for treatment and surveillance.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Angiomyolipoma; ARID1B; Mosaic; Neurodevelopmental disorders; TSC2; Tuberous sclerosis complex

DLG4-related synaptopathy: a new rare brain disorder - Rodriguez-Palmero, Agusti; Boerrigter, Melissa Maria; Gomez-Andres, David; Aldinger, Kimberly A.; Marcos-Alcalde, Inigo; Popp, Bernt; Everman, David B.; Lovgren, Alysia Kern; Arpin, Stephanie; Bahrambeigi, Vahid; Beunders, Gea; Bisgaard, Anne-Marie; et al. (Genetics in Medicine, 2021)
Purpose: Postsynaptic density protein-95 (PSD-95), encoded by DLG4, regulates excitatory synaptic function in the brain. Here we present the clinical and genetic features of 53 patients (42 previously unpublished) with DLG4 variants. Methods: The clinical and genetic information were collected through GeneMatcher collaboration. All the individuals were investigated by local clinicians and the gene variants were identified by clinical exome/genome sequencing. Results: The clinical picture was predominated by early onset global developmental delay, intellectual disability, autism spectrum disorder, and attention deficit–hyperactivity disorder, all of which point to a brain disorder. Marfanoid habitus, which was previously suggested to be a characteristic feature of DLG4-related phenotypes, was found in only nine individuals and despite some overlapping features, a distinct facial dysmorphism could not be established. Of the 45 different DLG4 variants, 39 were predicted to lead to loss of protein function and the majority occurred de novo (four with unknown origin). The six missense variants identified were suggested to lead to structural or functional changes by protein modeling studies. Conclusion: The present study shows that clinical manifestations associated with DLG4 overlap with those found in other neurodevelopmental disorders of synaptic dysfunction; thus, we designate this group of disorders as DLG4-related synaptopathy. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2021-03-05

DNA methylation episignature and comparative epigenomic profiling for Pitt-Hopkins syndrome caused by TCF4 variants - van der Laan, Liselot; Lauffer, Peter; Rooney, Kathleen; Silva, Ananília; Haghshenas, Sadegheh; Relator, Raissa; Levy, Michael A.; Trajkova, Slavica; Huisman, Sylvia A.; Bijlsma, Emilia K.; Kleefstra, Tjitske; van Bon, Bregje W.; et al. (Human Genetics and Genomics Advances, 2024)
Pitt-Hopkins syndrome (PTHS) is a neurodevelopmental disorder caused by pathogenic variants in TCF4, leading to intellectual disability, specific morphological features, and autonomic nervous system dysfunction. Epigenetic dysregulation has been implicated in PTHS, prompting the investigation of a DNA methylation (DNAm) “episignature” specific to PTHS for diagnostic purposes and variant reclassification and functional insights into the molecular pathophysiology of this disorder. A cohort of 67 individuals with genetically confirmed PTHS and three individuals with intellectual disability and a variant of uncertain significance (VUS) in TCF4 were studied. The DNAm episignature was developed with an Infinium Methylation EPIC BeadChip array analysis using peripheral blood cells. Support vector machine (SVM) modeling and clustering methods were employed to generate a DNAm classifier for PTHS. Validation was extended to an additional cohort of 11 individuals with PTHS. The episignature was assessed in relation to other neurodevelopmental disorders and its specificity was examined. A specific DNAm episignature for PTHS was established. The classifier exhibited high sensitivity for TCF4 haploinsufficiency and missense variants in the basic-helix-loop-helix domain. Notably, seven individuals with TCF4 variants exhibited negative episignatures, suggesting complexities related to mosaicism, genetic factors, and environmental influences. The episignature displayed degrees of overlap with other related disorders and biological pathways. This study defines a DNAm episignature for TCF4-related PTHS, enabling improved diagnostic accuracy and VUS reclassification. The finding that some cases scored negatively underscores the potential for multiple or nested episignatures and emphasizes the need for continued investigation to enhance specificity and coverage across PTHS-related variants.
CRIS-Team Scopus Importer:2024-05-10
Keywords: CNV; DNA methylation; episignature; neurodevelopmental disorder; Pitt-Hopkins syndrome; PTHS; TCF4; VUS

Do the exome: A case of Williams-Beuren syndrome with severe epilepsy due to a truncating de novo variant in GABRA1 - Popp, Bernt; Trollmann, Regina; Büttner, Christian; Caliebe, Almuth; Thiel, Christian; Hüffmeier, Ulrike; Reis, André; Zweier, Christiane (European Journal of Medical Genetics, 2016)
Williams-Beuren syndrome (WBS) is a relatively common, clinically recognizable microdeletion syndrome. In most cases the typical heterozygous deletion of 1.5 Mb on chromosome 7q11.23 spanning about 26 genes can be identified. Also some larger or smaller atypical deletions have been reported and associated with additional or atypical phenotypic aspects. We report on an individual with typical WBS due to the common deletion and with refractory infantile spasms. Using trio-exome sequencing, we identified a de novo truncating variant c.1200del, p (Lys401Serfs*25) in GABRA1 as the likely cause of the early onset epilepsy. This unique case not only allows to further define the phenotypic spectrum of infantile epileptic encephalopathy associated with rare de novo GABRA1 variants but exemplifies the need for a sensitive review of unclear associations in clinically defined syndromes and for extended diagnostic work-up in individuals with unusual presentations of a genetically confirmed diagnosis.
EVALuna2:9310

Early-onset parkinsonism in PPP2R5D-related neurodevelopmental disorder - Hetzelt, Katalin; Kerling, Frank; Kraus, Cornelia; Rauch, Christophe; Thiel, Christian; Winterholler, Martin; Reis, André; Zweier, Christiane (European Journal of Medical Genetics, 2021)
PPP2R5D-related neurodevelopmental disorder (NDD) is a rare autosomal-dominant disease with developmental delay and mild to severe intellectual disability. So far, fewer than 30 affected individuals with mostly recurrent, de novo missense variants in PPP2R5D were reported. Recently, parkinsonism with an onset between 20 and 40 years was reported in four adult individuals with the same p.(Glu200Lys) variant in PPP2R5D. By trio exome sequencing we now identified the variant p.(Glu198Lys) in a 29 year old woman presenting with typical clinical manifestations of PPP2R5D-related neurodevelopmental disorder and additionally with motor decline and levodopa responsive, early-onset parkinsonism from her mid-twenties on. Accordingly, a clear reduction of dopamine transporter in the striatum on both sides was revealed by brain scintigraphy. Our findings further expand the molecular and clinical spectrum of PPP2R5D-related NDD and confirm the association with parkinsonism in early adulthood. This has marked implications for prognosis of PPP2R5D-related NDDs and for the therapeutic management of motor decline and parkinson-like symptoms in affected individuals.
CRIS-Team Scopus Importer:2021-01-01
Keywords: Neurodevelopmental disorder; Parkinson's disease; Parkinsonism; PPP2R5D

EIF3F-related neurodevelopmental disorder: refining the phenotypic and expanding the molecular spectrum - Hüffmeier, Ulrike; Kraus, Cornelia; Reuter, Miriam; Uebe, Steffen; Abbott, Mary-Alice; Ahmed, Syed A.; Rawson, Kristyn L.; Barr, Eileen; Li, Hong; Bruel, Ange-Line; Faivre, Laurence; Mau-Them, Frederic Tran; et al. (Orphanet Journal of Rare Diseases, 2021)
Background: An identical homozygous missense variant in EIF3F, identified through a large-scale genome-wide sequencing approach, was reported as causative in nine individuals with a neurodevelopmental disorder, characterized by variable intellectual disability, epilepsy, behavioral problems and sensorineural hearing-loss. To refine the phenotypic and molecular spectrum of EIF3F-related neurodevelopmental disorder, we examined independent patients. Results: 21 patients were homozygous and one compound heterozygous for c.694T>G/p.(Phe232Val) in EIF3F. Haplotype analyses in 15 families suggested that c.694T>G/p.(Phe232Val) was a founder variant. All affected individuals had developmental delays including delayed speech development. About half of the affected individuals had behavioral problems, altered muscular tone, hearing loss, and short stature. Moreover, this study suggests that microcephaly, reduced sensitivity to pain, cleft lip/palate, gastrointestinal symptoms and ophthalmological symptoms are part of the phenotypic spectrum. Minor dysmorphic features were observed, although neither the individuals’ facial nor general appearance were obviously distinctive. Symptoms in the compound heterozygous individual with an additional truncating variant were at the severe end of the spectrum in regard to motor milestones, speech delay, organic problems and pre- and postnatal growth of body and head, suggesting some genotype–phenotype correlation. Conclusions: Our study refines the phenotypic and expands the molecular spectrum of EIF3F-related syndromic neurodevelopmental disorder.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Altered muscular tone; Behavioral difficulties; Deafness; EIF3F gene; Neurodevelopmental disorder; Short stature

EIF3F-related neurodevelopmental disorder: refining the phenotypic and expanding the molecular spectrum - Hüffmeier, Ulrike; Kraus, Cornelia; Reuter, Miriam; Uebe, Steffen; Abbott, Mary-Alice; Ahmed, Syed A.; Rawson, Kristyn L.; Barr, Eileen; Li, Hong; Bruel, Ange-Line; Faivre, Laurence; Them, Frederic Tran Mau; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

Eight further individuals with intellectual disability and epilepsy carrying bi-allelic CNTNAP2 aberrations allow delineation of the mutational and phenotypic spectrum - Smogavec, Mateja; Cleall, Alison; Hoyer, Juliane; Lederer, Damien; Nassogne, Marie-Cecile; Palmer, Elizabeth E.; Deprez, Marie; Benoit, Valerie; Maystadt, Isabelle; Noakes, Charlotte; Leal-Esquivel, Alejandro; Shaw, Marie; et al. (Journal of Medical Genetics, 2016)
Heterozygous copy number variants (CNVs) or sequence variants in the contactin-associated protein 2 gene CNTNAP2 have been discussed as risk factors for a wide spectrum of neurodevelopmental and neuropsychiatric disorders. Bi-allelic aberrations in this gene are causative for an autosomal-recessive disorder with epilepsy, severe intellectual disability (ID) and cortical dysplasia (CDFES). As the number of reported individuals is still limited, we aimed at a further characterisation of the full mutational and clinical spectrum.Targeted sequencing, chromosomal microarray analysis or multigene panel sequencing was performed in individuals with severe ID and epilepsy.We identified homozygous mutations, compound heterozygous CNVs or CNVs and mutations in CNTNAP2 in eight individuals from six unrelated families. All aberrations were inherited from healthy, heterozygous parents and are predicted to be deleterious for protein function. Epilepsy occurred in all affected individuals with onset in the first 3.5 years of life. Further common aspects were ID (severe in 6/8), regression of speech development (5/8) and behavioural anomalies (7/8). Interestingly, cognitive impairment in one of two affected brothers was, in comparison, relatively mild with good speech and simple writing abilities. Cortical dysplasia that was previously reported in CDFES was not present in MRIs of six individuals and only suspected in one.By identifying novel homozygous or compound heterozygous, deleterious CNVs and mutations in eight individuals from six unrelated families with moderate-to-severe ID, early onset epilepsy and behavioural anomalies, we considerably broaden the mutational and clinical spectrum associated with bi-allelic aberrations in CNTNAP2.
EVALuna2:9347

Encephalopathies with KCNC1 variants: genotype-phenotype-functional correlations - Cameron, Jillian M.; Maljevic, Snezana; Nair, Umesh; Aung, Ye Htet; Cogne, Benjamin; Bezieau, Stephane; Blair, Edward; Isidor, Bertrand; Zweier, Christiane; Reis, André; Koenig, Mary Kay; Maarup, Timothy; et al. (Annals of Clinical and Translational Neurology, 2019)
Objective To analyze clinical phenotypes associated with KCNC1 variants other than the Progressive Myoclonus Epilepsy-causing variant p.Arg320His, determine the electrophysiological functional impact of identified variants and explore genotype-phenotype-physiological correlations. Methods Ten cases with putative pathogenic variants in KCNC1 were studied. Variants had been identified via whole-exome sequencing or gene panel testing. Clinical phenotypic data were analyzed. To determine functional impact of variants detected in the K(v)3.1 channel encoded by KCNC1, Xenopus laevis oocyte expression system and automated two-electrode voltage clamping were used. Results Six unrelated patients had a Developmental and Epileptic Encephalopathy and a recurrent de novo variant p.Ala421Val (c.1262C > T). Functional analysis of p.Ala421Val revealed loss of function through a significant reduction in whole-cell current, but no dominant-negative effect. Three patients had a contrasting phenotype of Developmental Encephalopathy without seizures and different KCNC1 variants, all of which caused loss of function with reduced whole-cell currents. Evaluation of the variant p.Ala513Val (c.1538C > T) in the tenth case, suggested it was a variant of uncertain significance. Interpretation These are the first reported cases of Developmental and Epileptic Encephalopathy due to KCNC1 mutation. The spectrum of phenotypes associated with KCNC1 is now broadened to include not only a Progressive Myoclonus Epilepsy, but an infantile onset Developmental and Epileptic Encephalopathy, as well as Developmental Encephalopathy without seizures. Loss of function is a key feature, but definitive electrophysiological separation of these phenotypes has not yet emerged.
CRIS-Team WoS Importer:2019-07-16

Estimating the effect size of the 15Q11.2 BP1-BP2 deletion and its contribution to neurodevelopmental symptoms: recommendations for practice - Jønch, Aia Elise; Douard, Elise; Moreau, Clara; Van Dijck, Anke; Passeggeri, Marzia; Kooy, Frank; Puechberty, Jacques; Campbell, Carolyn; Sanlaville, Damien; Lefroy, Henrietta; Richetin, Sonia; Pain, Aurelie; et al. (Journal of Medical Genetics, 2019)
Background: The 15q11.2 deletion is frequently identified in the neurodevelopmental clinic. Case-control studies have associated the 15q11.2 deletion with neurodevelopmental disorders, and clinical case series have attempted to delineate a microdeletion syndrome with considerable phenotypic variability. The literature on this deletion is extensive and confusing, which is a challenge for genetic counselling. The aim of this study was to estimate the effect size of the 15q11.2 deletion and quantify its contribution to neurodevelopmental disorders. Methods: We performed meta-analyses on new and previously published case-control studies and used statistical models trained in unselected populations with cognitive assessments. We used new (n=241) and previously published (n=150) data from a clinically referred group of deletion carriers. 15q11.2 duplications (new n=179 and previously published n=35) were used as a neutral control variant. Results: The deletion decreases IQ by 4.3 points. The estimated ORs and respective frequencies in deletion carriers for intellectual disabilities, schizophrenia and epilepsy are 1.7 (3.4%), 1.5 (2%) and 3.1 (2.1%), respectively. There is no increased risk for heart malformations and autism. In the clinically referred group, the frequency and nature of symptoms in deletions are not different from those observed in carriers of the 15q11.2 duplication suggesting that most of the reported symptoms are due to ascertainment bias. Conclusions: We recommend that the deletion should be classified as € pathogenic of mild effect size'. Since it explains only a small proportion of the phenotypic variance in carriers, it is not worth discussing in the developmental clinic or in a prenatal setting.
CRIS-Team Scopus Importer:2019-09-27
Keywords: 15q11.2 copy-number variants; congenital heart disease; epilepsy; loss-of-function intolerance; neurodevelopmental disorders

Evolutionary conserved networks of human height identify multiple Mendelian causes of short stature - Hauer, Nadine; Popp, Bernt; Taher, Leila; Vogl, Carina; Dhandapany, Perundurai S.; Büttner, Christian; Uebe, Steffen; Sticht, Heinrich; Ferrazzi, Fulvia; Ekici, Arif Bülent; De Luca, Alessandro; Klinger, Patricia; et al. (European journal of human genetics, 2019)
Height is a heritable and highly heterogeneous trait. Short stature affects 3% of the population and in most cases is genetic in origin. After excluding known causes, 67% of affected individuals remain without diagnosis. To identify novel candidate genes for short stature, we performed exome sequencing in 254 unrelated families with short stature of unknown cause and identified variants in 63 candidate genes in 92 (36%) independent families. Based on systematic characterization of variants and functional analysis including expression in chondrocytes, we classified 13 genes as strong candidates. Whereas variants in at least two families were detected for all 13 candidates, two genes had variants in 6 (UBR4) and 8 (LAMA5) families, respectively. To facilitate their characterization, we established a clustered network of 1025 known growth and short stature genes, which yielded 29 significantly enriched clusters, including skeletal system development, appendage development, metabolic processes, and ciliopathy. Eleven of the candidate genes mapped to 21 of these clusters, including CPZ, EDEM3, FBRS, IFT81, KCND1, PLXNA3, RASA3, SLC7A8, UBR4, USP45, and ZFHX3. Fifty additional growth-related candidates we identified await confirmation in other affected families. Our study identifies Mendelian forms of growth retardation as an important component of idiopathic short stature.
CRIS-Team Scopus Importer:2019-05-24

Exome Pool-Seq in neurodevelopmental disorders - Popp, Bernt; Ekici, Arif Bülent; Thiel, Christian; Hoyer, Juliane; Wiesener, Antje; Kraus, Cornelia; Reis, André; Zweier, Christiane (European journal of human genetics, 2017)
High throughput sequencing has greatly advanced disease gene identification, especially in heterogeneous entities. Despite falling costs this is still an expensive and laborious technique, particularly when studying large cohorts. To address this problem we applied Exome Pool-Seq as an economic and fast screening technology in neurodevelopmental disorders (NDDs). Sequencing of 96 individuals can be performed in eight pools of 12 samples on less than one Illumina sequencer lane. In a pilot study with 96 cases we identified 27 variants, likely or possibly affecting function. Twenty five of these were identified in 923 established NDD genes (based on SysID database, status November 2016) (ACTB, AHDC1, ANKRD11, ATP6V1B2, ATRX, CASK, CHD8, GNAS, IFIH1, KCNQ2, KMT2A, KRAS, MAOA, MED12, MED13L, RIT1, SETD5, SIN3A, TCF4, TRAPPC11, TUBA1A, WAC, ZBTB18, ZMYND11), two in 543 (SysID) candidate genes (ZNF292, BPTF), and additionally a de novo loss-of-function variant in LRRC7, not previously implicated in NDDs. Most of them were confirmed to be de novo, but we also identified X-linked or autosomal-dominantly or autosomal-recessively inherited variants. With a detection rate of 28%, Exome Pool-Seq achieves comparable results to individual exome analyses but reduces costs by >85%. Compared with other large scale approaches using Molecular Inversion Probes (MIP) or gene panels, it allows flexible re-analysis of data. Exome Pool-Seq is thus well suited for large-scale, cost-efficient and flexible screening in characterized but heterogeneous entities like NDDs.
EVALuna2:9387

Exome Pool-Seq Reloaded - Popp, B.; Vasileiou, G.; Zweier, M.; Ekici, Arif Bülent; Moortgat, S.; Lederer, D.; Maystadt, I.; Destree, A.; Drunat, S.; Verloes, A.; Rauch, A.; Steindl, K.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Expanded phenotypic spectrum of neurodevelopmental and neurodegenerative disorder Bryant-Li-Bhoj syndrome with 38 additional individuals - Layo-Carris, Dana E.; Lubin, Emily E.; Sangree, Annabel K.; Clark, Kelly J.; Durham, Emily L.; Gonzalez, Elizabeth M.; Smith, Sarina; Angireddy, Rajesh; Wang, Xiao Min; Weiss, Erin; Toutain, Annick; Mendoza-Londono, Roberto; et al. (European Journal of Human Genetics, 2024)
Bryant-Li-Bhoj syndrome (BLBS), which became OMIM-classified in 2022 (OMIM: 619720, 619721), is caused by germline variants in the two genes that encode histone H3.3 (H3-3A/H3F3A and H3-3B/H3F3B) [1–4]. This syndrome is characterized by developmental delay/intellectual disability, craniofacial anomalies, hyper/hypotonia, and abnormal neuroimaging [1, 5]. BLBS was initially categorized as a progressive neurodegenerative syndrome caused by de novo heterozygous variants in either H3-3A or H3-3B [1–4]. Here, we analyze the data of the 58 previously published individuals along 38 unpublished, unrelated individuals. In this larger cohort of 96 people, we identify causative missense, synonymous, and stop-loss variants. We also expand upon the phenotypic characterization by elaborating on the neurodevelopmental component of BLBS. Notably, phenotypic heterogeneity was present even amongst individuals harboring the same variant. To explore the complex phenotypic variation in this expanded cohort, the relationships between syndromic phenotypes with three variables of interest were interrogated: sex, gene containing the causative variant, and variant location in the H3.3 protein. While specific genotype-phenotype correlations have not been conclusively delineated, the results presented here suggest that the location of the variants within the H3.3 protein and the affected gene (H3-3A or H3-3B) contribute more to the severity of distinct phenotypes than sex. Since these variables do not account for all BLBS phenotypic variability, these findings suggest that additional factors may play a role in modifying the phenotypes of affected individuals. Histones are poised at the interface of genetics and epigenetics, highlighting the potential role for gene-environment interactions and the importance of future research.
CRIS-Team Scopus Importer:2024-05-10

Expanding the clinical and molecular spectrum of the novel CYFIP2-related neurodevelopmental disorder and functional proof of aberrant WRC-mediated actin dynamics - Begemann, A.; Sticht, Heinrich; Mcwalter, K.; Vitobello, A.; Faivre, L.; Alhaddad, B.; Banka, S.; Becker, J.; Bierhals, T.; Brown, K.; Bruel, A.; Brunet, T.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Expanding the clinical and mutational spectrum of Kaufman oculocerebrofacial syndrome with biallelic UBE3B mutations - Basel-Vanagaite, Lina; Yilmaz, Rustem; Tang, Sha; Reuter, Miriam; Rahner, Nils; Grange, Dorothy K.; Mortenson, Megan; Koty, Patrick; Feenstra, Heather; Gonzalez, Kelly D. Farwell; Sticht, Heinrich; Boddaert, Nathalie; et al. (Human genetics, 2014)
Biallelic mutations of UBE3B have recently been shown to cause Kaufman oculocerebrofacial syndrome (also reported as blepharophimosis-ptosis-intellectual disability syndrome), an autosomal recessive condition characterized by hypotonia, developmental delay, intellectual disability, congenital anomalies, characteristic facial dysmorphic features, and low cholesterol levels. To date, six patients with either missense mutations affecting the UBE3B HECT domain or truncating mutations have been described. Here, we report on the identification of homozygous or compound heterozygous UBE3B mutations in six additional patients from five unrelated families using either targeted UBE3B sequencing in individuals with suggestive facial dysmorphic features, or exome sequencing. Our results expand the clinical and mutational spectrum of the UBE3B-related disorder in several ways. First, we have identified UBE3B mutations in individuals who previously received distinct clinical diagnoses: two sibs with Toriello-Carey syndrome as well as the patient reported to have a "new" syndrome by Buntinx and Majewski in 1990. Second, we describe the adult phenotype and clinical variability of the syndrome. Third, we report on the first instance of homozygous missense alterations outside the HECT domain of UBE3B, observed in a patient with mildly dysmorphic facial features. We conclude that UBE3B mutations cause a clinically recognizable and possibly underdiagnosed syndrome characterized by distinct craniofacial features, hypotonia, failure to thrive, eye abnormalities, other congenital malformations, low cholesterol levels, and severe intellectual disability. We review the UBE3B-associated phenotypes, including forms that can mimick Toriello-Carey syndrome, and suggest the single designation "Kaufman oculocerebrofacial syndrome".
EVALuna2:9227

Expanding the Phenotype Associated with NAA10-Related N-Terminal Acetylation Deficiency - Saunier, Chloe; Stove, Svein Isungset; Popp, Bernt; Gerard, Benedicte; Blenski, Marina; Ahmew, Nicholas; De Bie, Charlotte; Goldenberg, Paula; Isidor, Bertrand; Keren, Boris; Leheup, Bruno; Lampert, Laetitia; et al. (Human Mutation, 2016)
N-terminal acetylation is a common protein modification in eukaryotes associated with numerous cellular processes. Inherited mutations in NAA10, encoding the catalytic subunit of the major N-terminal acetylation complex NatA have been associated with diverse, syndromic X-linked recessive disorders, whereas de novo missense mutations have been reported in one male and one female individual with severe intellectual disability but otherwise unspecific phenotypes. Thus, the full genetic and clinical spectrum of NAA10 deficiency is yet to be delineated. We identified three different novel and one known missense mutation in NAA10, de novo in 11 females, and due to maternal germ line mosaicism in another girl and her more severely affected and deceased brother. In vitro enzymatic assays for the novel, recurrent mutations p.(Arg83Cys) and p.(Phe128Leu) revealed reduced catalytic activity. X-inactivation was random in five females. The core phenotype of X-linked NAA10-related N-terminal-acetyltransferase deficiency in both males and females includes developmental delay, severe intellectual disability, postnatal growth failure with severe microcephaly, and skeletal or cardiac anomalies. Genotype-phenotype correlations within and between both genders are complex and may include various factors such as location and nature of mutations, enzymatic stability and activity, and X-inactivation in females.
EVALuna2:9314

Expanding the spectrum of WDR62 mutations : description of new cases - Ruaud, L.; Drunat, S.; Ernault, A.; Capri, Y.; Van Maldergem, L.; Engel, C.; Altuzarra, C.; Bayat, A.; Moortgart, S.; Maystadt, I.; Abramowicz, M.; Zweier, Christiane; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

FOXP2 variants in 14 individuals with developmental speech and language disorders broaden the mutational and clinical spectrum - Reuter, Miriam; Riess, Angelika; Moog, Ute; Briggs, Tracy A.; Chandler, Kate E.; Rauch, Anita; Stampfer, Miriam; Steindl, Katharina; Glaeser, Dieter; Joset, Pascal; Krumbiegel, Mandy; Rabe, Harald; et al. (Journal of Medical Genetics, 2017)
Disruptions of the FOXP2 gene, encoding a forkhead transcription factor, are the first known monogenic cause of a speech and language disorder. So far, mainly chromosomal rearrangements such as translocations or larger deletions affecting FOXP2 have been reported. Intragenic deletions or convincingly pathogenic point mutations in FOXP2 have up to date only been reported in three families. We thus aimed at a further characterisation of the mutational and clinical spectrum.Chromosomal microarray testing, trio exome sequencing, multigene panel sequencing and targeted sequencing of FOXP2 were performed in individuals with variable developmental disorders, and speech and language deficits.We identified four different truncating mutations, two novel missense mutations within the forkhead domain and an intragenic deletion in FOXP2 in 14 individuals from eight unrelated families. Mutations occurred de novo in four families and were inherited from an affected parent in the other four. All index patients presented with various manifestations of language and speech impairment. Apart from two individuals with normal onset of speech, age of first words was between 4 and 7 years. Articulation difficulties such as slurred speech, dyspraxia, stuttering and poor pronunciation were frequently noted. Motor development was normal or only mildly delayed. Mild cognitive impairment was reported for most individuals.By identifying intragenic deletions or mutations in 14 individuals from eight unrelated families with variable developmental delay/cognitive impairment and speech and language deficits, we considerably broaden the mutational and clinical spectrum associated with aberrations in FOXP2.
EVALuna2:9348

Fruits of Genomic Match-making: De Novo Variants in PRR12 are Associated with a Spectrum of Eye and Neurodevelopmental Anomalies - Balci, T. B.; Wang, L.; Lalani, S.; Heide, S.; Keren, B.; Mignot, C.; Morley, G.; Walia, J.; Wheeler, P.; Lemons, J.; Buritica, D. Rodriguez; Riberi, E.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Further delineation of the female phenotype with KDM5C disease causing variants: 19 new individuals and review of the literature - Carmignac, Virginie; Nambot, Sophie; Lehalle, Daphne; Callier, Patrick; Moortgat, Stephanie; Benoit, Valerie; Ghoumid, Jamal; Delobel, Bruno; Smol, Thomas; Thuillier, Caroline; Zordan, Cecile; Naudion, Sophie; et al. (Clinical Genetics, 2020)
X-linked intellectual disability (XLID) is a genetically heterogeneous condition involving more than 100 genes. To date, 35 pathogenic variants have been reported in the lysine specific demethylase 5C (KDM5C) gene. KDM5C variants are one of the major causes of moderate to severe XLID. Affected males present with short stature, distinctive facial features, behavioral disorders, epilepsy, and spasticity. For most of these variants, related female carriers have been reported, but phenotypic descriptions were poor. Here, we present clinical and molecular features of 19 females carrying 10 novel heterozygous variants affecting KDM5C function, including five probands with de novo variants. Four heterozygous females were asymptomatic. All affected individuals presented with learning disabilities or ID (mostly moderate), and four also had a language impairment mainly affecting expression. Behavioral disturbances were frequent, and endocrine disorders were more frequent in females. In conclusion, our findings provide evidence of the role of KDM5C in ID in females highlighting the increasing implication of XLID genes in females, even in sporadic affected individuals. Disease expression of XLID in females should be taken into consideration for genetic counseling.
CRIS-Team Scopus Importer:2020-06-09
Keywords: data-sharing; exome; females; KDM5C; X-linked intellectual disability

Gain-of-function and loss-of-function variants in GRIA3 lead to distinct neurodevelopmental phenotypes. - Rinaldi, Berardo; Bayat, Allan; Zachariassen, Linda G.; Sun, Jia Hui; Ge, Yu Han; Zhao, Dan; Bonde, Kristine; Madsen, Laura H.; Awad, Ilham Abdimunim Ali; Bagiran, Duygu; Sbeih, Amal; Shah, Syeda Maidah; et al. (Brain, 2024)
AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid) receptors (AMPARs) mediate fast excitatory neurotransmission in the brain. AMPARs form by homo- or heteromeric assembly of subunits encoded by the GRIA1-GRIA4 genes, of which only GRIA3 is X-chromosomal. Increasing numbers of GRIA3 missense variants are reported in patients with neurodevelopmental disorders (NDD), but only a few have been examined functionally. Here, we evaluated the impact on AMPAR function of one frameshift and 43 rare missense GRIA3 variants identified in patients with NDD by electrophysiological assays. Thirty-one variants alter receptor function and show loss-of-function or gain-of-function properties, whereas 13 appeared neutral. We collected detailed clinical data from 25 patients (from 23 families) harbouring 17 of these variants. All patients had global developmental impairment, mostly moderate (9/25) or severe (12/25). Twelve patients had seizures, including focal motor (6/12), unknown onset motor (4/12), focal impaired awareness (1/12), (atypical) absence (2/12), myoclonic (5/12) and generalized tonic-clonic (1/12) or atonic (1/12) seizures. The epilepsy syndrome was classified as developmental and epileptic encephalopathy in eight patients, developmental encephalopathy without seizures in 13 patients, and intellectual disability with epilepsy in four patients. Limb muscular hypotonia was reported in 13/25, and hypertonia in 10/25. Movement disorders were reported in 14/25, with hyperekplexia or non-epileptic erratic myoclonus being the most prevalent feature (8/25). Correlating receptor functional phenotype with clinical features revealed clinical features for GRIA3-associated NDDs and distinct NDD phenotypes for loss-of-function and gain-of-function variants. Gain-of-function variants were associated with more severe outcomes: patients were younger at the time of seizure onset (median age: 1 month), hypertonic and more often had movement disorders, including hyperekplexia. Patients with loss-of-function variants were older at the time of seizure onset (median age: 16 months), hypotonic and had sleeping disturbances. Loss-of-function and gain-of-function variants were disease-causing in both sexes but affected males often carried de novo or hemizygous loss-of-function variants inherited from healthy mothers, whereas affected females had mostly de novo heterozygous gain-of-function variants.
EVALuna2:555553

Genetic and neurodevelopmental spectrum of SYNGAP1-associated intellectual disability and epilepsy - Mignot, Cyril; Von Stuelpnagel, Celina; Nava, Caroline; Ville, Dorothee; Sanlaville, Damien; Lesca, Gaetan; Rastetter, Agnes; Gachet, Benoit; Marie, Yannick; Korenke, G. Christoph; Borggraefe, Ingo; Hoffmann-Zacharska, Dorota; et al. (Journal of Medical Genetics, 2016)
We aimed to delineate the neurodevelopmental spectrum associated with SYNGAP1 mutations and to investigate genotype-phenotype correlations.We sequenced the exome or screened the exons of SYNGAP1 in a total of 251 patients with neurodevelopmental disorders. Molecular and clinical data from patients with SYNGAP1 mutations from other centres were also collected, focusing on developmental aspects and the associated epilepsy phenotype. A review of SYNGAP1 mutations published in the literature was also performed.We describe 17 unrelated affected individuals carrying 13 different novel loss-of-function SYNGAP1 mutations. Developmental delay was the first manifestation of SYNGAP1-related encephalopathy; intellectual disability became progressively obvious and was associated with autistic behaviours in eight patients. Hypotonia and unstable gait were frequent associated neurological features. With the exception of one patient who experienced a single seizure, all patients had epilepsy, characterised by falls or head drops due to atonic or myoclonic seizures, (myoclonic) absences and/or eyelid myoclonia. Triggers of seizures were frequent (n=7). Seizures were pharmacoresistant in half of the patients. The severity of the epilepsy did not correlate with the presence of autistic features or with the severity of cognitive impairment. Mutations were distributed throughout the gene, but spared spliced 3' and 5' exons. Seizures in patients with mutations in exons 4-5 were more pharmacoresponsive than in patients with mutations in exons 8-15.SYNGAP1 encephalopathy is characterised by early neurodevelopmental delay typically preceding the onset of a relatively recognisable epilepsy comprising generalised seizures (absences, myoclonic jerks) and frequent triggers.
EVALuna2:9321

Genetic and phenotypic spectrum associated with IFIH1 gain-of-function - Rice, Gillian; Park, Sehoon; Gavazzi, Francesco; Adang, Laura A.; Ayuk, Loveline A.; Van Eyck, Lien; Seabra, Luis; Barrea, Christophe; Battini, Roberta; Belot, Alexandre; Berg, Stefan; De Villemeur, Thierry Billette; et al. (Human Mutation, 2020)
IFIH1 gain-of-function has been reported as a cause of a type I interferonopathy encompassing a spectrum of autoinflammatory phenotypes including Aicardi-Goutieres syndrome and Singleton Merten syndrome. Ascertaining patients through a European and North American collaboration, we set out to describe the molecular, clinical and interferon status of a cohort of individuals with pathogenic heterozygous mutations in IFIH1. We identified 74 individuals from 51 families segregating a total of 27 likely pathogenic mutations in IFIH1. Ten adult individuals, 13.5% of all mutation carriers, were clinically asymptomatic (with seven of these aged over 50 years). All mutations were associated with enhanced type I interferon signaling, including six variants (22%) which were predicted as benign according to multiple in silico pathogenicity programs. The identified mutations cluster close to the ATP binding region of the protein. These data confirm variable expression and nonpenetrance as important characteristics of the IFIH1 genotype, a consistent association with enhanced type I interferon signaling, and a common mutational mechanism involving increased RNA binding affinity or decreased efficiency of ATP hydrolysis and filament disassembly rate.
CRIS-Team WoS Importer:2020-01-28

Genetic interaction screen for severe neurodevelopmental disorders reveals a functional link between Ube3a and Mef2 in Drosophila melanogaster - Straub, Jonas; Gregor, Anne; Sauerer, Tatjana; Fliedner, Anna; Distel, Laila; Suchy, Christine; Ekici, Arif Bülent; Ferrazzi, Fulvia; Zweier, Christiane (Scientific Reports, 2020)
Neurodevelopmental disorders (NDDs) are clinically and genetically extremely heterogeneous with shared phenotypes often associated with genes from the same networks. Mutations in TCF4, MEF2C, UBE3A, ZEB2 or ATRX cause phenotypically overlapping, syndromic forms of NDDs with severe intellectual disability, epilepsy and microcephaly. To characterize potential functional links between these genes/proteins, we screened for genetic interactions in Drosophila melanogaster. We induced ubiquitous or tissue specific knockdown or overexpression of each single orthologous gene (Da, Mef2, Ube3a, Zfh1, XNP) and in pairwise combinations. Subsequently, we assessed parameters such as lethality, wing and eye morphology, neuromuscular junction morphology, bang sensitivity and climbing behaviour in comparison between single and pairwise dosage manipulations. We found most stringent evidence for genetic interaction between Ube3a and Mef2 as simultaneous dosage manipulation in different tissues including glia, wing and eye resulted in multiple phenotype modifications. We subsequently found evidence for physical interaction between UBE3A and MEF2C also in human cells. Systematic pairwise assessment of the Drosophila orthologues of five genes implicated in clinically overlapping, severe NDDs and subsequent confirmation in a human cell line revealed interactions between UBE3A/Ube3a and MEF2C/Mef2, thus contributing to the characterization of the underlying molecular commonalities.<br
Keywords: Genetic interaction; Medical genetics; Molecular medicine; Neurodevelopmental disorders

Genetic Interaction screen for severe neurodevelopmental disorders reveals a functional link between Ube3a and Mef2 in Drosophila melanogaster - Straub, Jonas; Sauerer, Tatjana; Fliedner, Anna; Distel, Laila; Suchy, C.; Ekici, Arif Bülent; Ferrazzi, Fulvia; Gregor, Anne; Zweier, Christiane (52nd Conference of the European-Society-of-Human-Genetics (ESHG), 2019)
CRIS-Team WoS Importer:2019-10-25

Genetic screening confirms heterozygous mutations in ACAN as a major cause of idiopathic short stature - Hauer, Nadine; Sticht, Heinrich; Boppudi, Sangamitra; Büttner, Christian; Kraus, Cornelia; Trautmann, Udo; Zenker, Martin; Zweier, Christiane; Wiesener, Antje; Abou Jamra, Rami; Wieczorek, Dagmar; Kelkel, Jaqueline; et al. (Scientific Reports, 2017)
Short stature is a common pediatric disorder affecting 3% of the population. However, the clinical variability and genetic heterogeneity prevents the identification of the underlying cause in about 80% of the patients. Recently, heterozygous mutations in the ACAN gene coding for the proteoglycan aggrecan, a main component of the cartilage matrix, were associated with idiopathic short stature. To ascertain the prevalence of ACAN mutations and broaden the phenotypic spectrum in patients with idiopathic short stature we performed sequence analyses in 428 families. We identified heterozygous nonsense mutations in four and potentially disease-causing missense variants in two families (1.4%). These patients presented with a mean of -3.2 SDS and some suggestive clinical characteristics. The results suggest heterozygous mutations in ACAN as a common cause of isolated as well as inherited idiopathic short stature.
EVALuna2:9379

Genotype–phenotype correlations and novel molecular insights into the DHX30-associated neurodevelopmental disorders - Mannucci, Ilaria; Dang, Nghi D. P.; Huber, Hannes; Murry, Jaclyn B.; Abramson, Jeff; Althoff, Thorsten; Banka, Siddharth; Baynam, Gareth; Bearden, David; Beleza-Meireles, Ana; Benke, Paul J.; Berland, Siren; et al. (Genome Medicine, 2021)
Background: We aimed to define the clinical and variant spectrum and to provide novel molecular insights into the DHX30-associated neurodevelopmental disorder. Methods: Clinical and genetic data from affected individuals were collected through Facebook-based family support group, GeneMatcher, and our network of collaborators. We investigated the impact of novel missense variants with respect to ATPase and helicase activity, stress granule (SG) formation, global translation, and their effect on embryonic development in zebrafish. SG formation was additionally analyzed in CRISPR/Cas9-mediated DHX30-deficient HEK293T and zebrafish models, along with in vivo behavioral assays. Results: We identified 25 previously unreported individuals, ten of whom carry novel variants, two of which are recurrent, and provide evidence of gonadal mosaicism in one family. All 19 individuals harboring heterozygous missense variants within helicase core motifs (HCMs) have global developmental delay, intellectual disability, severe speech impairment, and gait abnormalities. These variants impair the ATPase and helicase activity of DHX30, trigger SG formation, interfere with global translation, and cause developmental defects in a zebrafish model. Notably, 4 individuals harboring heterozygous variants resulting either in haploinsufficiency or truncated proteins presented with a milder clinical course, similar to an individual harboring a de novo mosaic HCM missense variant. Functionally, we established DHX30 as an ATP-dependent RNA helicase and as an evolutionary conserved factor in SG assembly. Based on the clinical course, the variant location, and type we establish two distinct clinical subtypes. DHX30 loss-of-function variants cause a milder phenotype whereas a severe phenotype is caused by HCM missense variants that, in addition to the loss of ATPase and helicase activity, lead to a detrimental gain-of-function with respect to SG formation. Behavioral characterization of dhx30-deficient zebrafish revealed altered sleep-wake activity and social interaction, partially resembling the human phenotype. Conclusions: Our study highlights the usefulness of social media to define novel Mendelian disorders and exemplifies how functional analyses accompanied by clinical and genetic findings can define clinically distinct subtypes for ultra-rare disorders. Such approaches require close interdisciplinary collaboration between families/legal representatives of the affected individuals, clinicians, molecular genetics diagnostic laboratories, and research laboratories.
CRIS-Team Scopus Importer:2021-06-11

Habituation Learning Is a Widely Affected Mechanism in Drosophila Models of Intellectual Disability and Autism Spectrum Disorders - Fenckova, Michaela; Blok, Laura E.R.; Asztalos, Lenke; Goodman, David P.; Cizek, Pavel; Singgih, Euginia L.; Glennon, Jeffrey C.; IntHout, Joanna; Zweier, Christiane; Eichler, Evan E.; von Reyn, Catherine R.; Bernier, Raphael A.; et al. (Biological Psychiatry, 2019)
Background: Although habituation is one of the most ancient and fundamental forms of learning, its regulators and its relevance for human disease are poorly understood. Methods: We manipulated the orthologs of 286 genes implicated in intellectual disability (ID) with or without comorbid autism spectrum disorder (ASD) specifically in Drosophila neurons, and we tested these models in light-off jump habituation. We dissected neuronal substrates underlying the identified habituation deficits and integrated genotype–phenotype annotations, gene ontologies, and interaction networks to determine the clinical features and molecular processes that are associated with habituation deficits. Results: We identified >100 genes required for habituation learning. For 93 of these genes, a role in habituation learning was previously unknown. These genes characterize ID disorders with macrocephaly and/or overgrowth and comorbid ASD. Moreover, individuals with ASD from the Simons Simplex Collection carrying damaging de novo mutations in these genes exhibit increased aberrant behaviors associated with inappropriate, stereotypic speech. At the molecular level, ID genes required for normal habituation are enriched in synaptic function and converge on Ras/mitogen-activated protein kinase (Ras/MAPK) signaling. Both increased Ras/MAPK signaling in gamma-aminobutyric acidergic (GABAergic) neurons and decreased Ras/MAPK signaling in cholinergic neurons specifically inhibit the adaptive habituation response. Conclusions: Our work supports the relevance of habituation learning to ASD, identifies an unprecedented number of novel habituation players, supports an emerging role for inhibitory neurons in habituation, and reveals an opposing, circuit-level-based mechanism for Ras/MAPK signaling. These findings establish habituation as a possible, widely applicable functional readout and target for pharmacologic intervention in ID/ASD.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Autism spectrum disorder; Drosophila; GABAergic neurons; Habituation learning; Intellectual disability; Ras/MAPK

Haploinsufficiency of NR4A2 is associated with a neurodevelopmental phenotype with prominent language impairment - Reuter, Miriam; Krumbiegel, Mandy; Schlueter, Gregor; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2017)
Non-recurrent deletions in 2q24.1, minimally overlapping two genes, NR4A2 and GPD2, were recently described in individuals with language impairment and behavioral and cognitive symptoms. We herewith report on a female patient with a similar phenotype of severe language and mild cognitive impairment, in whom we identified a de novo deletion covering only NR4A2. NR4A2 encodes a transcription factor highly expressed in brain regions critical for speech and language and implicated in dopaminergic neuronal development. Our findings of a de novo deletion of NR4A2 in an individual with mild intellectual disability and prominent speech and language impairment provides further evidence for NR4A2 haploinsufficiency being causative for neurodevelopmental and particularly language phenotypes.
EVALuna2:9359

Haploinsufficiency of PRR12 causes a spectrum of neurodevelopmental, eye, and multisystem abnormalities - Chowdhury, Fuad; Wang, Lei; Al-Raqad, Mohammed; Amor, David J.; Baxová, Alice; Bendová, Šárka; Biamino, Elisa; Brusco, Alfredo; Caluseriu, Oana; Cox, Nancy J.; Froukh, Tawfiq; Gunay-Aygun, Meral; et al. (Genetics in Medicine, 2021)
Purpose: Proline Rich 12 (PRR12) is a gene of unknown function with suspected DNA-binding activity, expressed in developing mice and human brains. Predicted loss-of-function variants in this gene are extremely rare, indicating high intolerance of haploinsufficiency. Methods: Three individuals with intellectual disability and iris anomalies and truncating de novo PRR12 variants were described previously. We add 21 individuals with similar PRR12 variants identified via matchmaking platforms, bringing the total number to 24. Results: We observed 12 frameshift, 6 nonsense, 1 splice-site, and 2 missense variants and one patient with a gross deletion involving PRR12. Three individuals had additional genetic findings, possibly confounding the phenotype. All patients had developmental impairment. Variable structural eye defects were observed in 12/24 individuals (50%) including anophthalmia, microphthalmia, colobomas, optic nerve and iris abnormalities. Additional common features included hypotonia (61%), heart defects (52%), growth failure (54%), and kidney anomalies (35%). PrediXcan analysis showed that phecodes most strongly associated with reduced predicted PRR12 expression were enriched for eye- (7/30) and kidney- (4/30) phenotypes, such as wet macular degeneration and chronic kidney disease. Conclusion: These findings support PRR12 haploinsufficiency as a cause for a novel disorder with a wide clinical spectrum marked chiefly by neurodevelopmental and eye abnormalities.
CRIS-Team Scopus Importer:2021-04-16

Haploinsufficiency of the Chromatin Remodeler BPTF Causes Syndromic Developmental and Speech Delay, Postnatal Microcephaly, and Dysmorphic Features - Stankiewicz, Pawel; Khan, Tahir N.; Szafranski, Przemyslaw; Slattery, Leah; Streff, Haley; Vetrini, Francesco; Bernstein, Jonathan A.; Brown, Chester W.; Rosenfeld, Jill A.; Rednam, Surya; Scollon, Sarah; Bergstrom, Katie L.; et al. (American Journal of Human Genetics, 2017)
Bromodomain PHD finger transcription factor (BPTF) is the largest subunit of nucleosome remodeling factor (NURF), a member of the ISWI chromatin-remodeling complex. However, the clinical consequences of disruption of this complex remain largely uncharacterized. BPTF is required for anterior-posterior axis formation of the mouse embryo and was shown to promote posterior neuroectodermal fate by enhancing Smad2-activated wnt8 expression in zebrafish. Here, we report eight loss-of-function and two missense variants (eight de novo and two of unknown origin) in BPTF on 17q24.2. The BPTF variants were found in unrelated individuals aged between 2.1 and 13 years, who manifest variable degrees of developmental delay/intellectual disability (10/10), speech delay (10/10), postnatal microcephaly (7/9), and dysmorphic features (9/10). Using CRISPR-Cas9 genome editing of bptf in zebrafish to induce a loss of gene function, we observed a significant reduction in head size of F0 mutants compared to control larvae. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) and phospho-histone H3 (PH3) staining to assess apoptosis and cell proliferation, respectively, showed a significant increase in cell death in F0 mutants compared to controls. Additionally, we observed a substantial increase of the ceratohyal angle of the craniofacial skeleton in bptf F0 mutants, indicating abnormal craniofacial patterning. Taken together, our data demonstrate the pathogenic role of BPTF haploinsufficiency in syndromic neurodevelopmental anomalies and extend the clinical spectrum of human disorders caused by ablation of chromatin remodeling complexes.
EVALuna2:9361

Identification and characterization of a GLMN splice site variant in a family with glomuvenous malformations - Skowronek, Dariush; Hebebrand, Moritz; Erber, Ramona; Agaimy, Abbas; Zweier, Christiane; Felbor, Ute; Rath, Matthias (European Journal of Dermatology, 2020)
CRIS-Team Scopus Importer:2020-06-26

Identification and characterization of a GLMN splice site variant in a three-generation-family with glomuvenous malformations - Skowronek, D.; Hebebrand, Moritz; Erber, Ramona; Agaimy, Abbas; Zweier, Christiane; Felbor, U.; Rath, M. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

In-depth characterisation of a cohort of individuals with missense and loss-of-function variants disrupting FOXP2 - Morison, Lottie D.; Meffert, Elisabeth; Stampfer, Miriam; Steiner-Wilke, Irene; Vollmer, Brigitte; Schulze, Katrin; Briggs, Tracy; Braden, Ruth; Vogel, Adam; Thompson-Lake, Daisy; Patel, Chirag; Blair, Edward; et al. (Journal of Medical Genetics, 2022)
BackgroundHeterozygous disruptions of FOXP2 were the first identified molecular cause for severe speech disorder: childhood apraxia of speech (CAS), and yet few cases have been reported, limiting knowledge of the condition. MethodsHere we phenotyped 28 individuals from 17 families with pathogenic FOXP2-only variants (12 loss-of-function, five missense variants; 14 males; aged 2 to 62 years). Health and development (cognitive, motor, social domains) were examined, including speech and language outcomes with the first cross-linguistic analysis of English and German. ResultsSpeech disorders were prevalent (23/25, 92%) and CAS was most common (22/25, 88%), with similar speech presentations across English and German. Speech was still impaired in adulthood, and some speech sounds (eg, 'th', 'r', 'ch', 'j') were never acquired. Language impairments (21/25, 84%) ranged from mild to severe. Comorbidities included feeding difficulties in infancy (10/27, 37%), fine (13/26, 50%) and gross (13/26, 50%) motor impairment, anxiety (5/27, 19%), depression (6/27, 22%) and sleep disturbance (11/15, 44%). Physical features were common (22/27, 81%) but with no consistent pattern. Cognition ranged from average to mildly impaired and was incongruent with language ability; for example, seven participants with severe language disorder had average non-verbal cognition. ConclusionsAlthough we identify an increased prevalence of conditions like anxiety, depression and sleep disturbance, we confirm that the consequences of FOXP2 dysfunction remain relatively specific to speech disorder, as compared with other recently identified monogenic conditions associated with CAS. Thus, our findings reinforce that FOXP2 provides a valuable entry point for examining the neurobiological bases of speech disorder.
CRIS-Team WoS Importer:2022-11-25

Intellectual disability and autism spectrum disorders 'on the fly': insights from Drosophila - Coll-Tane, Mireia; Krebbers, Alina; Castells-Nobau, Anna; Zweier, Christiane; Schenck, Annette (Disease Models & Mechanisms, 2019)
Intellectual disability (ID) and autism spectrum disorders (ASD) are frequently co-occurring neurodevelopmental disorders and affect 2-3% of the population. Rapid advances in exome and genome sequencing have increased the number of known implicated genes by threefold, to more than a thousand. The main challenges in the field are now to understand the various pathomechanisms associated with this bewildering number of genetic disorders, to identify new genes and to establish causality of variants in still-undiagnosed cases, and to work towards causal treatment options that so far are available only for a few metabolic conditions. To meet these challenges, the research community needs highly efficient model systems. With an increasing number of relevant assays and rapidly developing novel methodologies, the fruit fly Drosophila melanogaster is ideally positioned to change gear in ID and ASD research. The aim of this Review is to summarize some of the exciting work that already has drawn attention to Drosophila as a model for these disorders. We highlight well-established ID-and ASD-relevant fly phenotypes at the (sub) cellular, brain and behavioral levels, and discuss strategies of how this extraordinarily efficient and versatile model can contribute to 'next generation' medical genomics and to a better understanding of these disorders.
CRIS-Team WoS Importer:2019-06-21

Intrafamilial neurological phenotypic variability due to either biallelic or monoallelic pathogenic variants in CACNA1A - Mammadova, Dilbar; Kraus, Cornelia; Leis, Thomas; Popp, Bernt; Zweier, Christiane; Reis, André; Trollmann, Regina (Frontiers in Neurology, 2024)
Pathogenic heterozygous variants in CACNA1A are associated with familial hemiplegic migraine, episodic ataxia type 2 and spinocerebellar ataxia type 6, and more recently, neurodevelopmental disorders. We describe a severe, early-onset phenotype including severe muscular hypotonia, early-onset epileptic seizures, apnoea, optic atrophy and dysphagia in three siblings carrying compound heterozygous frameshift variants in CACNA1A. Two male patients died at the age of 5 or 14 months of suspected SIDS or severe developmental epileptic encephalopathy (DEE) with refractory seizures and apnoea. A male child (index patient) developed severe early-onset DEE including seizures and ictal apnoea at the age of 4 weeks. Another male child developed generalized epilepsy and mild intellectual impairment in late infancy, and his mother and his maternal uncle were identified as carriers of a known CACNA1A pathogenic variant [c.2602delG heterozygous, p. (Ala868Profs*24)] with a diagnosis of episodic ataxia type 2. This maternal pathogenic variant c.2602delG was detected in the index patient and child 2. Trio-Exome sequencing identified an additional heterozygous pathogenic variant in the CACNA1A gene, c.5476delC, p.(His1826Thrfs*30) in the index patient and child 2, which was inherited from the asymptomatic father. In conclusion, the novel compound heterozygosity for two frameshift pathogenic variants, maternally [c.2602delG, p.(Ala868Profs*24)] and paternally [c.5476delC, p.(His1826Thrfs*3)] is associated with a severe phenotype of early-onset DEE. This observation highlights the necessity of additional analyses to clarify unusual phenotypes even if a pathogenic variant has already been identified, and expands the clinical spectrum of CACNA1A-related disorders.
CRIS-Team Scopus Importer:2024-10-25
Keywords: apneic spells; burst suppression; developmental epileptic encephalopathy; early-onset epileptic encephalopathy; generalized epilepsy; optic nerve atrophy

Investigating PHF13 induced infertility through single cell transcriptomics and non-vertebrate model organisms - Bosch, Elisabeth; Lukassen, S.; Gregor, Anne; Ekici, Arif Bülent; Zweier, Christiane; Winterpacht, Andreas (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Loss-of-function variants of SETD5 cause intellectual disability and the core phenotype of microdeletion 3p25.3 syndrome - Kuechler, Alma; Zink, Alexander M.; Wieland, Thomas; Luedecke, Hermann-Josef; Cremer, Kirsten; Salviati, Leonardo; Magini, Pamela; Najafi, Kimia; Zweier, Christiane; Czeschik, Johanna Christina; Aretz, Stefan; Endele, Sabine; et al. (European journal of human genetics, 2015)
Intellectual disability (ID) has an estimated prevalence of 2-3%. Due to its extreme heterogeneity, the genetic basis of ID remains elusive in many cases. Recently, whole exome sequencing (WES) studies revealed that a large proportion of sporadic cases are caused by de novo gene variants. To identify further genes involved in ID, we performed WES in 250 patients with unexplained ID and their unaffected parents and included exomes of 51 previously sequenced child-parents trios in the analysis. Exome analysis revealed de novo intragenic variants in SET domain-containing 5 (SETD5) in two patients. One patient carried a nonsense variant, and the other an 81 bp deletion located across a splice-donor site. Chromosomal microarray diagnostics further identified four de novo non-recurrent microdeletions encompassing SETD5. CRISPR/Cas9 mutation modelling of the two intragenic variants demonstrated nonsense-mediated decay of the resulting transcripts, pointing to a loss-of-function (LoF) and haploinsufficiency as the common disease-causing mechanism of intragenic SETD5 sequence variants and SETD5-containing microdeletions. In silico domain prediction of SETD5, a predicted SET domain-containing histone methyltransferase (HMT), substantiated the presence of a SET domain and identified a novel putative PHD domain, strengthening a functional link to well-known histone-modifying ID genes. All six patients presented with ID and certain facial dysmorphisms, suggesting that SETD5 sequence variants contribute substantially to the microdeletion 3p25.3 phenotype. The present report of two SETD5 LoF variants in 301 patients demonstrates a prevalence of 0.7% and thus SETD5 variants as a relatively frequent cause of ID.
EVALuna2:9248

Loss of PHF6 leads to aberrant development of human neuron-like cells - Fliedner, Anna; Gregor, Anne; Ferrazzi, Fulvia; Ekici, Arif Bülent; Sticht, Heinrich; Zweier, Christiane (Scientific Reports, 2020)
Pathogenic variants in PHD finger protein 6 (PHF6) cause Borjeson–Forssman–Lehmann syndrome (BFLS), a rare X-linked neurodevelopmental disorder, which manifests variably in both males and females. To investigate the mechanisms behind overlapping but distinct clinical aspects between genders, we assessed the consequences of individual variants with structural modelling and molecular techniques. We found evidence that de novo variants occurring in females are more severe and result in loss of PHF6, while inherited variants identified in males might be hypomorph or have weaker effects on protein stability. This might contribute to the different phenotypes in male versus female individuals with BFLS. Furthermore, we used CRISPR/Cas9 to induce knockout of PHF6 in SK-N-BE (2) cells which were then differentiated to neuron-like cells in order to model nervous system related consequences of PHF6 loss. Transcriptome analysis revealed a broad deregulation of genes involved in chromatin and transcriptional regulation as well as in axon and neuron development. Subsequently, we could demonstrate that PHF6 is indeed required for proper neuron proliferation, neurite outgrowth and migration. Impairment of these processes might therefore contribute to the neurodevelopmental and cognitive dysfunction in BFLS.
CRIS-Team Scopus Importer:2020-11-13

Manifestation of epilepsy in a patient with EED-related overgrowth (Cohen-Gibson syndrome) - Hetzelt, Katalin; Winterholler, Martin; Kerling, Frank; Rauch, Christophe; Ekici, Arif Bülent; Winterpacht, Andreas; Vasileiou, Georgia; Uebe, Steffen; Thiel, Christian; Kraus, Cornelia; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2021)
Cohen-Gibson syndrome is a rare genetic disorder, characterized by fetal or early childhood overgrowth and mild to severe intellectual disability. It is caused by heterozygous aberrations in EED, which encodes an evolutionary conserved polycomb group (PcG) protein that forms the polycomb repressive complex-2 (PRC2) together with EZH2, SUZ12, and RBBP7/4. In total, 11 affected individuals with heterozygous pathogenic variants in EED were reported, so far. All variants affect a few key residues within the EED WD40 repeat domain. By trio exome sequencing, we identified the heterozygous missense variant c.581A > G, p.(Asn194Ser) in exon 6 of the EED-gene in an individual with moderate intellectual disability, overgrowth, and epilepsy. The same pathogenic variant was detected in 2 of the 11 previously reported cases. Epilepsy, however, was only diagnosed in one other individual with Cohen-Gibson syndrome before. Our findings further confirm that the WD40 repeat domain represents a mutational hotspot; they also expand the clinical spectrum of Cohen-Gibson syndrome and highlight the clinical variability even in individuals with the same pathogenic variant. Furthermore, they indicate a possible association between Cohen-Gibson syndrome and epilepsy.
CRIS-Team WoS Importer:2021-09-24

Mechanism of KMT5B haploinsufficiency in neurodevelopment in humans and mice - Sheppard, Sarah E.; Bryant, Laura; Wickramasekara, Rochelle N.; Vaccaro, Courtney; Robertson, Brynn; Hallgren, Jodi; Hulen, Jason; Watson, Cynthia J.; Faundes, Victor; Duffourd, Yannis; Lee, Pearl; Celeste Simon, M.; et al. (Science Advances, 2023)
Pathogenic variants in KMT5B, a lysine methyltransferase, are associated with global developmental delay, macrocephaly, autism, and congenital anomalies (OMIM# 617788). Given the relatively recent discovery of this disorder, it has not been fully characterized. Deep phenotyping of the largest (n = 43) patient cohort to date identified that hypotonia and congenital heart defects are prominent features that were previously not associated with this syndrome. Both missense variants and putative loss-of-function variants resulted in slow growth in patient-derived cell lines. KMT5B homozygous knockout mice were smaller in size than their wild-type littermates but did not have significantly smaller brains, suggesting relative macrocephaly, also noted as a prominent clinical feature. RNA sequencing of patient lymphoblasts and Kmt5b haploinsufficient mouse brains identified differentially expressed pathways associated with nervous system development and function including axon guidance signaling. Overall, we identified additional pathogenic variants and clinical features in KMT5Brelated neurodevelopmental disorder and provide insights into the molecular mechanisms of the disorder using multiple model systems.
CRIS-Team Scopus Importer:2023-03-24

Microphthalmia is not a mandatory finding in X-linked recessive syndromic microphthalmia caused by the recurrent BCOR variant p.Pro85Leu - Kraus, Cornelia; Uebe, Steffen; Thiel, Christian; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2018)
Mutations in BCOR cause X-linked dominant and X-linked recessive forms of syndromic microphthalmia. By exome sequencing, we identified the recurrent BCOR mutation p.Pro85Leu in two brothers and their unaffected mother. While the older brother's phenotype completely fits the described phenotypic spectrum of X-linked recessive BCOR-associated Lenz microphthalmia syndrome, the younger brother showed developmental delay, microcephaly, and skeletal anomalies, but not the key feature of microphthalmia. In contrast to the previously published families, our findings demonstrate a large variability of BCOR-associated, syndromic phenotypes, indicating incomplete penetrance of p.Pro85Leu with regards to microphthalmia in males.
EVALuna2:34843

Missense variants in NDD-associated FBXO11 impair its localization and Fbxo11 deficiency leads to neuronal impairment in Drosophila melanogaster - Gregor, Anne; Meerbrei, T.; Distel, Luitpold; Gerstner, T.; Gupta, A.; Toutain, A.; Lynch, S. A.; Maxton, C.; Lemke, J. R.; Bernat, J. A.; Bombei, H. M.; Foulds, N.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Missense Variants in RHOBTB2 Cause a Developmental and Epileptic Encephalopathy in Humans, and Altered Levels Cause Neurological Defects in Drosophila - Straub, Jonas; Konrad, Enrico; Grüner, Johanna; Toutain, Annick; Bok, Levinus A.; Cho, Megan T.; Crawford, Heather P.; Dubbs, Holly; Douglas, Ganka; Jobling, Rebekah; Johnson, Diana; Krock, Bryan; et al. (American Journal of Human Genetics, 2018)
Although the role of typical Rho GTPases and other Rho-linked proteins in synaptic plasticity and cognitive function and dysfunction is widely acknowledged, the role of atypical Rho GTPases (such as RHOBTB2) in neurodevelopment has barely been characterized. We have now identified de novo missense variants clustering in the BTB-domain-encoding region of RHOBTB2 in ten individuals with a similar phenotype, including early-onset epilepsy, severe intellectual disability, postnatal microcephaly, and movement disorders. Three of the variants were recurrent. Upon transfection of HEK293 cells, we found that mutant RHOBTB2 was more abundant than the wild-type, most likely because of impaired degradation in the proteasome. Similarly, elevated amounts of the Drosophila ortholog RhoBTB in vivo were associated with seizure susceptibility and severe locomotor defects. Knockdown of RhoBTB in the Drosophila dendritic arborization neurons resulted in a decreased number of dendrites, thus suggesting a role of RhoBTB in dendritic development. We have established missense variants in the BTB-domain-encoding region of RHOBTB2 as causative for a developmental and epileptic encephalopathy and have elucidated the role of atypical Rho GTPase RhoBTB in Drosophila neurological function and possibly dendrite development.
EVALuna2:33715

Mutations affecting the SAND domain of DEAF1 cause intellectual disability with severe speech impairment and behavioral problems - Vulto-Van Silfhout, Anneke T.; Rajamanickam, Shivakumar; Jensik, Philip J.; Vergult, Sarah; De Rocker, Nina; Newhall, Kathryn J.; Raghavan, Ramya; Reardon, Sara N.; Jarrett, Kelsey; Mcintyre, Tara; Bulinski, Joseph; Ownby, Stacy L.; et al. (American Journal of Human Genetics, 2014)
Recently, we identified in two individuals with intellectual disability (ID) different de novo mutations in DEAF1, which encodes a transcription factor with an important role in embryonic development. To ascertain whether these mutations in DEAF1 are causative for the ID phenotype, we performed targeted resequencing of DEAF1 in an additional cohort of over 2,300 individuals with unexplained ID and identified two additional individuals with de novo mutations in this gene. All four individuals had severe ID with severely affected speech development, and three showed severe behavioral problems. DEAF1 is highly expressed in the CNS, especially during early embryonic development. All four mutations were missense mutations affecting the SAND domain of DEAF1. Altered DEAF1 harboring any of the four amino acid changes showed impaired transcriptional regulation of the DEAF1 promoter. Moreover, behavioral studies in mice with a conditional knockout of Deaf1 in the brain showed memory deficits and increased anxiety-like behavior. Our results demonstrate that mutations in DEAF1 cause ID and behavioral problems, most likely as a result of impaired transcriptional regulation by DEAF1.
EVALuna2:9219

New insights into the clinical and molecular spectrum of the novel CYFIP2-related neurodevelopmental disorder and impairment of the WRC-mediated actin dynamics - Begemann, Anaïs; Sticht, Heinrich; Begtrup, Amber; Vitobello, Antonio; Faivre, Laurence; Banka, Siddharth; Alhaddad, Bader; Asadollahi, Reza; Becker, Jessica; Bierhals, Tatjana; Brown, Kathleen E.; Bruel, Ange Line; et al. (Genetics in Medicine, 2020)
Purpose: A few de novo missense variants in the cytoplasmic FMRP-interacting protein 2 (CYFIP2) gene have recently been described as a novel cause of severe intellectual disability, seizures, and hypotonia in 18 individuals, with p.Arg87 substitutions in the majority. Methods: We assembled data from 19 newly identified and all 18 previously published individuals with CYFIP2 variants. By structural modeling and investigation of WAVE-regulatory complex (WRC)-mediated actin polymerization in six patient fibroblast lines we assessed the impact of CYFIP2 variants on the WRC. Results: Sixteen of 19 individuals harbor two previously described and 11 novel (likely) disease-associated missense variants. We report p.Asp724 as second mutational hotspot (4/19 cases). Genotype–phenotype correlation confirms a consistently severe phenotype in p.Arg87 patients but a more variable phenotype in p.Asp724 and other substitutions. Three individuals with milder phenotypes carry putative loss-of-function variants, which remain of unclear pathogenicity. Structural modeling predicted missense variants to disturb interactions within the WRC or impair CYFIP2 stability. Consistent with its role in WRC-mediated actin polymerization we substantiate aberrant regulation of the actin cytoskeleton in patient fibroblasts. Conclusion: Our study expands the clinical and molecular spectrum of CYFIP2-related neurodevelopmental disorder and provides evidence for aberrant WRC-mediated actin dynamics as contributing cellular pathomechanism.
CRIS-Team Scopus Importer:2020-11-13
Keywords: CYFIP2; epilepsy; intellectual disability; WASF; WAVE-regulatory complex (WRC)

NRF1 association with AUTS2-Polycomb mediates specific gene activation in the brain - Liu, Sanxiong; Aldinger, Kimberly A.; Cheng, Chi Vicky; Kiyama, Takae; Dave, Mitali; McNamara, Hanna K.; Zhao, Wukui; Stafford, James M.; Descostes, Nicolas; Lee, Pedro; Caraffi, Stefano G.; Ivanovski, Ivan; et al. (Molecular Cell, 2021)
The heterogeneous family of complexes comprising Polycomb repressive complex 1 (PRC1) is instrumental for establishing facultative heterochromatin that is repressive to transcription. However, two PRC1 species, ncPRC1.3 and ncPRC1.5, are known to comprise novel components, AUTS2, P300, and CK2, that convert this repressive function to that of transcription activation. Here, we report that individuals harboring mutations in the HX repeat domain of AUTS2 exhibit defects in AUTS2 and P300 interaction as well as a developmental disorder reflective of Rubinstein-Taybi syndrome, which is mainly associated with a heterozygous pathogenic variant in CREBBP/EP300. Moreover, the absence of AUTS2 or mutation in its HX repeat domain gives rise to misregulation of a subset of developmental genes and curtails motor neuron differentiation of mouse embryonic stem cells. The transcription factor nuclear respiratory factor 1 (NRF1) has a novel and integral role in this neurodevelopmental process, being required for ncPRC1.3 recruitment to chromatin.
CRIS-Team Scopus Importer:2021-11-26
Keywords: active transcription; AUTS2; brain development; ncPRC1.3; NRF1; P300; polycomb; RSTS

Phenotype and genotype of 87 patients with Mowat-Wilson syndrome and recommendations for care - Ivanovski, Ivan; Djuric, Olivera; Caraffi, Stefano Giuseppe; Santodirocco, Daniela; Pollazzon, Marzia; Rosato, Simonetta; Cordelli, Duccio Maria; Abdalla, Ebtesam; Accorsi, Patrizia; Adam, Margaret P.; Ajmone, Paola Francesca; Badura-Stronka, Magdalena; et al. (Genetics in Medicine, 2018)
PURPOSE: Mowat-Wilson syndrome (MWS) is a rare intellectual disability/multiple congenital anomalies syndrome caused by heterozygous mutation of the ZEB2 gene. It is generally underestimated because its rarity and phenotypic variability sometimes make it difficult to recognize. Here, we aimed to better delineate the phenotype, natural history, and genotype-phenotype correlations of MWS. METHODS: In a collaborative study, we analyzed clinical data for 87 patients with molecularly confirmed diagnosis. We described the prevalence of all clinical aspects, including attainment of neurodevelopmental milestones, and compared the data with the various types of underlying ZEB2 pathogenic variations. RESULTS: All anthropometric, somatic, and behavioral features reported here outline a variable but highly consistent phenotype. By presenting the most comprehensive evaluation of MWS to date, we define its clinical evolution occurring with age and derive suggestions for patient management. Furthermore, we observe that its severity correlates with the kind of ZEB2 variation involved, ranging from ZEB2 locus deletions, associated with severe phenotypes, to rare nonmissense intragenic mutations predicted to preserve some ZEB2 protein functionality, accompanying milder clinical presentations. CONCLUSION: Knowledge of the phenotypic spectrum of MWS and its correlation with the genotype will improve its detection rate and the prediction of its features, thus improving patient care.
EVALuna2:34827

Phenotypic presentation of two additional individuals with heterozygous variants in BRSK2 - Kemmer, H.; Popp, B.; Verloes, A.; Horn, D.; Holtgrewe, M.; Zweier, Christiane; Ehmke, N. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Phenotypic spectrum and transcriptomic profile associated with germline variants in TRAF7 - Castilla-Vallmanya, Laura; Selmer, Kaja K.; Dimartino, Clemantine; Rabionet, Raquel; Blanco-Sanchez, Bernardo; Yang, Sandra; Reijnders, Margot R. F.; Van Essen, Antonie J.; Oufadem, Myriam; Vigeland, Magnus D.; Stadheim, Barbro; Houge, Gunnar; et al. (Genetics in Medicine, 2020)
Purpose Somatic variants in tumor necrosis factor receptor-associated factor 7 (TRAF7) cause meningioma, while germline variants have recently been identified in seven patients with developmental delay and cardiac, facial, and digital anomalies. We aimed to define the clinical and mutational spectrum associated with TRAF7 germline variants in a large series of patients, and to determine the molecular effects of the variants through transcriptomic analysis of patient fibroblasts. Methods We performed exome, targeted capture, and Sanger sequencing of patients with undiagnosed developmental disorders, in multiple independent diagnostic or research centers. Phenotypic and mutational comparisons were facilitated through data exchange platforms. Whole-transcriptome sequencing was performed on RNA from patient- and control-derived fibroblasts. Results We identified heterozygous missense variants in TRAF7 as the cause of a developmental delay-malformation syndrome in 45 patients. Major features include a recognizable facial gestalt (characterized in particular by blepharophimosis), short neck, pectus carinatum, digital deviations, and patent ductus arteriosus. Almost all variants occur in the WD40 repeats and most are recurrent. Several differentially expressed genes were identified in patient fibroblasts. Conclusion We provide the first large-scale analysis of the clinical and mutational spectrum associated with the TRAF7 developmental syndrome, and we shed light on its molecular etiology through transcriptome studies.
CRIS-Team WoS Importer:2020-05-22

Phoniatric, audiological, orodental and speech problems in a boy with cardio-facio-cutaneous syndrome type 3 (Cfc 3) due to a pathogenic variant in map2k1 – case study - Kosztyla-Hojna, Bozena; Borys, Jan; Zdrojkowski, Maciej; Duchnowska, Emilia; Kraszewska, Anna; Wasilewska, Daria; Zweier, Christiane; Midro, Alina Teresa (The Application of Clinical Genetics, 2021)
Cardio-facio-cutaneous syndrome 3 (CFC3) due to variants in MAP2K1 is a rare genetic disorder manifested mainly by short stature, facial dysmorphism, abnormalities of the cardiovascular system, skin changes, and intellectual disability. The aim of the study is the evaluation of the occurrence of pathological changes in the upper respiratory tract, orthodontic disorders, as well as voice, speech and hearing abnormalities in an 11-year-old boy with CFC3 syndrome. The lack of detailed diagnostics of speech, voice and hearing disorders, as well as the degree of their severity was an inspiration to undertake research in this field. Pathological changes in face, oral cavity, upper respiratory tract (nose, naso-pharynx, larynx), and hearing organ, as well as voice and speech quality, were assessed in an 11-year-old boy with CFC3 syndrome. Pathologies of the upper respiratory tract (adenoid hypertrophy, narrowing of the nasal passages) and laryngeal asymmetry were found without significant changes in voice quality in the acoustic examination, except for the voice timbre change confirmed in narrowband spectrography. Complex audiological assessment confirmed the existence of bilateral sensorineural hearing loss. Speech pathology assessment revealed abnormalities in the structure of articulation organ, its decreased motor efficiency, impreci-sion, reduced coordination, as well as the presence of autistic features. Exome sequencing showed the heterozygous variant c.371C>T (p.Pro124Leu) in the MAP2K1 gene, previously described as pathogenic, thus supporting a causative relevance. Phoniatric, audiological, orodental and speech problems should be considered as features of cardio-facio-cutaneous syndrome type 3 (CFC 3) phenotype due to a pathogenic variant in MAP2K1.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Articulation; Cardio-facio-cutaneous syndrome; Hearing loss; MAP2K1; Voice disorders

Prenatal diagnosis of HNF1B-associated renal cysts: Is there a need to differentiate intragenic variants from 17q12 microdeletion syndrome? - Vasileiou, Georgia; Hoyer, Juliane; Thiel, Christian; Schaefer, Jan Thomas; Zapke, Maren; Krumbiegel, Mandy; Kraus, Cornelia; Zweier, Markus; Uebe, Steffen; Ekici, Arif Bülent; Schneider, Michael; Wiesener, Michael; et al. (Prenatal Diagnosis, 2019)
Objective 17q12 microdeletions containing HNF1B and intragenic variants within this gene are associated with variable developmental, endocrine, and renal anomalies, often already noted prenatally as hyperechogenic/cystic kidneys. Here, we describe prenatal and postnatal phenotypes of seven individuals with HNF1B aberrations and compare their clinical and genetic data to those of previous studies. Methods Prenatal sequencing and postnatal chromosomal microarray analysis were performed in seven individuals with renal and/or neurodevelopmental phenotypes. We evaluated HNF1B-related clinical features from 82 studies and reclassified 192 reported intragenic HNF1B variants. Results In a prenatal case, we identified a novel in-frame deletion p.(Gly239del) within the HNF1B DNA-binding domain, a mutational hot spot as demonstrated by spatial clustering analysis and high computational prediction scores. The six postnatally diagnosed individuals harbored 17q12 microdeletions. Literature screening revealed variable reporting of HNF1B-associated clinical traits. Overall, both mutation groups showed a high phenotypic heterogeneity. The reclassification of all previously reported intragenic HNF1B variants provided an up-to-date overview of the mutational spectrum. Conclusions We highlight the value of prenatal HNF1B screening in renal developmental diseases. Standardized clinical reporting and systematic classification of HNF1B variants are necessary for a more accurate risk quantification of prenatal and postnatal clinical features, improving genetic counseling and prenatal decision making.
CRIS-Team WoS Importer:2019-11-08

PRICKLE2 revisited—further evidence implicating PRICKLE2 in neurodevelopmental disorders - Bayat, Allan; Iqbal, Sumaiya; Borredy, Kim; Amiel, Jeanne; Zweier, Christiane; Barcia, Guilia; Kraus, Cornelia; Weyhreter, Heike; Bassuk, Alexander G.; Chopra, Maya; Rubboli, Guido; Moller, Rikke S. (European journal of human genetics, 2021)
PRICKLE2 encodes a member of a highly conserved family of proteins that are involved in the non-canonical Wnt and planar cell polarity signaling pathway. Prickle2 localizes to the post-synaptic density, and interacts with post-synaptic density protein 95 and the NMDA receptor. Loss-of-function variants in prickle2 orthologs cause seizures in flies and mice but evidence for the role of PRICKLE2 in human disease is conflicting. Our goal is to provide further evidence for the role of this gene in humans and define the phenotypic spectrum of PRICKLE2-related disorders. We report a cohort of six subjects from four unrelated families with heterozygous rare PRICKLE2 variants (NM_198859.4). Subjects were identified through an international collaboration. Detailed phenotypic and genetic assessment of the subjects were carried out and in addition, we assessed the variant pathogenicity using bioinformatic approaches. We identified two missense variants (c.122 C > T; p.(Pro41Leu), c.680 C > G; p.(Thr227Arg)), one nonsense variant (c.214 C > T; p.(Arg72*) and one frameshift variant (c.1286_1287delGT; p.(Ser429Thrfs*56)). While the p.(Ser429Thrfs*56) variant segregated with disease in a family with three affected females, the three remaining variants occurred de novo. Subjects shared a mild phenotype characterized by global developmental delay, behavioral difficulties ± epilepsy, autistic features, and attention deficit hyperactive disorder. Computational analysis of the missense variants suggest that the altered amino acid residues are likely to be located in protein regions important for function. This paper demonstrates that PRICKLE2 is involved in human neuronal development and that pathogenic variants in PRICKLE2 cause neurodevelopmental delay, behavioral difficulties and epilepsy in humans.
CRIS-Team Scopus Importer:2021-06-18

QRICH1 variants in Ververi-Brady syndrome-delineation of the genotypic and phenotypic spectrum - Foehrenbach, Melanie; Jamra, Rami Abou; Borkhardt, Arndt; Brozou, Triantafyllia; Muschke, Petra; Popp, Bernt; Rey, Linda K.; Schaper, Joerg; Surowy, Harald; Zenker, Martin; Zweier, Christiane; Wieczorek, Dagmar; et al. (Clinical Genetics, 2020)
Ververi-Brady syndrome (VBS, # 617982) is a rare developmental disorder, and loss-of-function variants in QRICH1 were implicated in its etiology. Furthermore, a recognizable phenotype was proposed comprising delayed speech, learning difficulties and dysmorphic signs. Here, we present four unrelated individuals with one known nonsense variant (c.1954C > T; p.[Arg652*]) and three novel de novo QRICH1 variants, respectively. These included two frameshift mutations (c.832_833del; p.(Ser278Leufs*25), c.1812_1813delTG; p.(Glu605Glyfs*25)) and interestingly one missense mutation (c.2207G > A; p.[Ser736Asn]), expanding the mutational spectrum. Enlargement of the cohort by these four individuals contributes to the delineation of the VBS phenotype and suggests expressive speech delay, moderate motor delay, learning difficulties/mild ID, mild microcephaly, short stature and notable social behavior deficits as clinical hallmarks. In addition, one patient presented with nephroblastoma. The possible involvement of QRICH1 in pediatric cancer assumes careful surveillance a key priority for outcome of these patients. Further research and enlargement of cohorts are warranted to learn about the genetic architecture and the phenotypic spectrum in more detail.
CRIS-Team WoS Importer:2020-11-27

Rare deleterious mutations of HNRNP genes result in shared neurodevelopmental disorders - Gillentine, Madelyn A.; Wang, Tianyun; Hoekzema, Kendra; Rosenfeld, Jill; Liu, Pengfei; Guo, Hui; Kim, Chang N.; De Vries, Bert B. A.; Vissers, Lisenka E. L. M.; Nordenskjold, Magnus; Kvarnung, Malin; Lindstrand, Anna; et al. (Genome Medicine, 2021)
Background With the increasing number of genomic sequencing studies, hundreds of genes have been implicated in neurodevelopmental disorders (NDDs). The rate of gene discovery far outpaces our understanding of genotype-phenotype correlations, with clinical characterization remaining a bottleneck for understanding NDDs. Most disease-associated Mendelian genes are members of gene families, and we hypothesize that those with related molecular function share clinical presentations. Methods We tested our hypothesis by considering gene families that have multiple members with an enrichment of de novo variants among NDDs, as determined by previous meta-analyses. One of these gene families is the heterogeneous nuclear ribonucleoproteins (hnRNPs), which has 33 members, five of which have been recently identified as NDD genes (HNRNPK, HNRNPU, HNRNPH1, HNRNPH2, and HNRNPR) and two of which have significant enrichment in our previous meta-analysis of probands with NDDs (HNRNPU and SYNCRIP). Utilizing protein homology, mutation analyses, gene expression analyses, and phenotypic characterization, we provide evidence for variation in 12 HNRNP genes as candidates for NDDs. Seven are potentially novel while the remaining genes in the family likely do not significantly contribute to NDD risk. Results We report 119 new NDD cases (64 de novo variants) through sequencing and international collaborations and combined with published clinical case reports. We consider 235 cases with gene-disruptive single-nucleotide variants or indels and 15 cases with small copy number variants. Three hnRNP-encoding genes reach nominal or exome-wide significance for de novo variant enrichment, while nine are candidates for pathogenic mutations. Comparison of HNRNP gene expression shows a pattern consistent with a role in cerebral cortical development with enriched expression among radial glial progenitors. Clinical assessment of probands (n = 188-221) expands the phenotypes associated with HNRNP rare variants, and phenotypes associated with variation in the HNRNP genes distinguishes them as a subgroup of NDDs. Conclusions Overall, our novel approach of exploiting gene families in NDDs identifies new HNRNP-related disorders, expands the phenotypes of known HNRNP-related disorders, strongly implicates disruption of the hnRNPs as a whole in NDDs, and supports that NDD subtypes likely have shared molecular pathogenesis. To date, this is the first study to identify novel genetic disorders based on the presence of disorders in related genes. We also perform the first phenotypic analyses focusing on related genes. Finally, we show that radial glial expression of these genes is likely critical during neurodevelopment. This is important for diagnostics, as well as developing strategies to best study these genes for the development of therapeutics.
CRIS-Team WoS Importer:2021-05-21

Report 2018 of the Syndrome Day Committee - Zweier, Christiane (Medizinische Genetik, 2019)
EVALuna2:206987

SCAF4 loss of function in humans and Drosophila implicates mRNA transcriptional termination in neuro-developmental disorders - Fliedner, Anna; Kirchner, P.; Agre, K. E.; De Graaf-Van De Laar, I.; Clarke, M. Dutra; Davis-Keppen, L.; Ekici, Arif Bülent; Gregor, Anne; Lippa, N.; Mcwalter, K.; Mirzaa, G.; Noh, G.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Skeletal abnormalities are common features in Ayme-Gripp syndrome - Niceta, Marcello; Barbuti, Domenico; Gupta, Neerja; Ruggiero, Carlos; Tizzano, Eduardo F.; Graul-Neumann, Luitgard; Barresi, Sabina; Nishimura, Gen; Valenzuela, Irene; Lopez-Grondona, Fermina; Fernandez-Alvarez, Paula; Leoni, Chiara; et al. (Clinical Genetics, 2019)
Ayme-Gripp syndrome (AYGRPS) is a recognizable condition caused by a restricted spectrum of dominantly acting missense mutations affecting the transcription factor MAF. Major clinical features of AYGRPS include congenital cataracts, sensorineural hearing loss, intellectual disability, and a distinctive flat facial appearance. Skeletal abnormalities have also been observed in affected individuals, even though these features have not been assessed systematically. Expanding the series with four additional patients, here we provide a more accurate delineation of the molecular aspects and clinical phenotype, particularly focusing on the skeletal features characterizing this disorder. Apart from previously reported malar flattening and joint limitations, we document that carpal/tarsal and long bone defects, and hip dysplasia occur in affected subjects more frequently than formerly appreciated.
CRIS-Team WoS Importer:2019-11-15

Skeletal defects and defective osteoclast and osteoblast function in Ayme-Gripp syndrome - Niceta, M.; Del Fattore, A.; Barbuti, D.; Rossi, M.; Stellacci, E.; Gupta, N.; Ruggiero, C.; Tizzano, E.; Graul-Neumann, L.; Leoni, C.; Zweier, Christiane; Fernandez Alvarez, P.; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

STAG1 mutations cause a novel cohesinopathy characterised by unspecific syndromic intellectual disability - Lehalle, Daphne; Mosca-Boidron, Anne-Laure; Begtrup, Amber; Boute-Benejean, Odile; Charles, Perrine; Cho, Megan T.; Clarkson, Amanda; Devinsky, Orrin; Duffourd, Yannis; Duplomb-Jego, Laurence; Gerard, Benedicte; Jacquette, Aurelia; et al. (Journal of Medical Genetics, 2017)
Cohesinopathies are rare neurodevelopmental disorders arising from a dysfunction in the cohesin pathway, which enables chromosome segregation and regulates gene transcription. So far, eight genes from this pathway have been reported in human disease. STAG1 belongs to the STAG subunit of the core cohesin complex, along with five other subunits. This work aimed to identify the phenotype ascribed to STAG1 mutations.Among patients referred for intellectual disability (ID) in genetics departments worldwide, array-comparative genomic hybridisation (CGH), gene panel, whole-exome sequencing or whole-genome sequencing were performed following the local diagnostic standards.A mutation in STAG1 was identified in 17 individuals from 16 families, 9 males and 8 females aged 2-33 years. Four individuals harboured a small microdeletion encompassing STAG1; three individuals from two families had an intragenic STAG1 deletion. Six deletions were identified by array-CGH, one by whole-exome sequencing. Whole-exome sequencing found de novo heterozygous missense or frameshift STAG1 variants in eight patients, a panel of genes involved in ID identified a missense and a frameshift variant in two individuals. The 17 patients shared common facial features, with wide mouth and deep-set eyes. Four individuals had mild microcephaly, seven had epilepsy.We report an international series of 17 individuals from 16 families presenting with syndromic unspecific ID that could be attributed to a STAG1 deletion or point mutation. This first series reporting the phenotype ascribed to mutation in STAG1 highlights the importance of data sharing in the field of rare disorders.
EVALuna2:9353

Systematic Phenomics Analysis Deconvolutes Genes Mutated in Intellectual Disability into Biologically Coherent Modules - Kochinke, Korinna; Zweier, Christiane; Nijhof, Bonnie; Fenckova, Michaela; Cizek, Pavel; Honti, Frank; Keerthikumar, Shivakumar; Oortveld, Merel A. W.; Kleefstra, Tjitske; Kramer, Jamie M.; Webber, Caleb; Huynen, Martijn A.; et al. (American Journal of Human Genetics, 2016)
Intellectual disability (ID) disorders are genetically and phenotypically extremely heterogeneous. Can this complexity be depicted in a comprehensive way as a means of facilitating the understanding of ID disorders and their underlying biology? We provide a curated database of 746 currently known genes, mutations in which cause ID (ID-associated genes [ID-AGs]), classified according to ID manifestation and associated clinical features. Using this integrated resource, we show that ID-AGs are substantially enriched with co-expression, protein-protein interactions, and specific biological functions. Systematic identification of highly enriched functional themes and phenotypes revealed typical phenotype combinations characterizing process-defined groups of ID disorders, such as chromatin-related disorders and deficiencies in DNA repair. Strikingly, phenotype classification efficiently breaks down ID-AGs into subsets with significantly elevated biological coherence and predictive power. Custom-made functional Drosophila datasets revealed further characteristic phenotypes among ID-AGs and specific clinical classes. Our study and resource provide systematic insights into the molecular and clinical landscape of ID disorders, represent a significant step toward overcoming current limitations in ID research, and prove the utility of systematic human and cross-species phenomics analyses in highly heterogeneous genetic disorders.
EVALuna2:9318

TCF4 (E2-2) harbors tumor suppressive functions in SHH medulloblastoma - Hellwig, Malte; Lauffer, Marlen C.; Bockmayr, Michael; Spohn, Michael; Merk, Daniel J.; Harrison, Luke; Ahlfeld, Julia; Kitowski, Annabel; Neumann, Julia E.; Ohli, Jasmin; Holdhof, Doerthe; Niesen, Judith; et al. (Acta Neuropathologica, 2019)
The TCF4 gene encodes for the basic helix-loop-helix transcription factor 4 (TCF4), which plays an important role in the development of the central nervous system (CNS). Haploinsufficiency of TCF4 was found to cause Pitt-Hopkins syndrome (PTHS), a severe neurodevelopmental disorder. Recently, the screening of a large cohort of medulloblastoma (MB), a highly aggressive embryonal brain tumor, revealed almost 20% of adult patients with MB of the Sonic hedgehog (SHH) subtype carrying somatic TCF4 mutations. Interestingly, many of these mutations have previously been detected as germline mutations in patients with PTHS. We show here that overexpression of wild-type TCF4 in vitro significantly suppresses cell proliferation in MB cells, whereas mutant TCF4 proteins do not to the same extent. Furthermore, RNA sequencing revealed significant upregulation of multiple well-known tumor suppressors upon expression of wild-type TCF4. In vivo, a prenatal knockout of Tcf4 in mice caused a significant increase in apoptosis accompanied by a decreased proliferation and failed migration of cerebellar granule neuron precursor cells (CGNP), which are thought to be the cells of origin for SHH MB. In contrast, postnatal in vitro and in vivo knockouts of Tcf4 with and without an additional constitutive activation of the SHH pathway led to significantly increased proliferation of CGNP or MB cells. Finally, publicly available data from human MB show that relatively low expression levels of TCF4 significantly correlate with a worse clinical outcome. These results not only point to time-specific roles of Tcf4 during cerebellar development but also suggest a functional linkage between TCF4 mutations and the formation of SHH MB, proposing that TCF4 acts as a tumor suppressor during postnatal stages of cerebellar development.
CRIS-Team WoS Importer:2019-04-04

Tetrasomy of SCN2A associated with refractory neonatal epileptic encephalopathy - Krumbiegel, Mandy; Trollmann, Regina; Mammadova, Dilbar; Schnell, Alexander; Kraus, Cornelia; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

The Bavarian Ethics Committee for Pre-Implantation Diagnosis-811 Decisions Over 5 Years - Genzel-Boroviczeny, Orsolya; Bannasch, Thomas; Baeuml, Josef; Friedrich, Orsolya; Hellemann, Joachim; Kress, Wolfram; Magdefrau, Carola; Manzeschke, Arne; Pettinger, Joseph; Pogarell, Oliver; Rieger-Fackeldey, Esther; Robin, Dunja; et al. (Deutsches Ärzteblatt international, 2021)
CRIS-Team WoS Importer:2021-04-23

The recurrent TCF4 missense variant p.(Arg389Cys) causes a neurodevelopmental disorder overlapping with but not typical for Pitt-Hopkins syndrome - Popp, Bernt; Bienvenu, Thierry; Giurgea, Irina; Metreau, Julia; Kraus, Cornelia; Reis, André; Fischer, Jan; Bralo, Maria Palomares; Tenorio-Castano, Jair; Lapunzina, Pablo; Almoguera, Berta; Lopez-Grondona, Fermina; et al. (Clinical Genetics, 2022)
TCF4 haploinsufficiency by deletions, truncating variants or loss-of-function missense variants within the DNA-binding and protein interacting bHLH domain causes Pitt-Hopkins syndrome (PTHS). This neurodevelopmental disorder (NDD) is characterized by severe intellectual disability (ID), epilepsy, hyperbreathing and a typical facial gestalt. Only few aberrations of the N-terminus of TCF4 were associated with milder or atypical phenotypes. By personal communication and searching databases we assembled six cases with the novel, recurrent, de novo missense variant c.1165C > T, p.(Arg389Cys) in TCF4. This variant was identified by diagnostic exome or panel sequencing and is located upstream of the bHLH domain. All six individuals presented with moderate to severe ID with language impairment. Microcephaly occurred in two individuals, epilepsy only in one, and no breathing anomalies or myopia were reported. Facial gestalt showed some aspects of PTHS but was rather non-specific in most individuals. Interestingly, the variant is located within the AD2 activation domain next to a highly conserved coactivator-recruitment motif and might alter interaction with coactivator proteins independently from the bHLH domain. Our findings of a recurrent missense variant outside the bHLH domain in six individuals with an ID phenotype overlapping with but not typical for PTHS delineate a novel genotype-phenotype correlation for TCF4-related NDDs.
CRIS-Team WoS Importer:2022-09-02

Transcriptional repressor ZEB2 promotes terminal differentiation of CD8+ effector and memory T cell populations during infection - Omilusik, Kyla D.; Best, J. Adam; Yu, Bingfei; Goossens, Steven; Weidemann, Alexander; Nguyen, Jessica V.; Seuntjens, Eve; Stryjewska, Agata; Zweier, Christiane; Roychoudhuri, Rahul; Gattinoni, Luca; Bird, Lynne M.; et al. (Journal of Experimental Medicine, 2015)
ZEB2 is a multi-zinc-finger transcription factor known to play a significant role in early neurogenesis and in epithelial-mesenchymal transition-dependent tumor metastasis. Although the function of ZEB2 in T lymphocytes is unknown, activity of the closely related family member ZEB1 has been implicated in lymphocyte development. Here, we find that ZEB2 expression is up-regulated by activated T cells, specifically in the KLRG1(hi) effector CD8(+) T cell subset. Loss of ZEB2 expression results in a significant loss of antigen-specific CD8(+) T cells after primary and secondary infection with a severe impairment in the generation of the KLRG1(hi) effector memory cell population. We show that ZEB2, which can bind DNA at tandem, consensus E-box sites, regulates gene expression of several E-protein targets and may directly repress Il7r and Il2 in CD8(+) T cells responding to infection. Furthermore, we find that T-bet binds to highly conserved T-box sites in the Zeb2 gene and that T-bet and ZEB2 regulate similar gene expression programs in effector T cells, suggesting that T-bet acts upstream and through regulation of ZEB2. Collectively, we place ZEB2 in a larger transcriptional network that is responsible for the balance between terminal differentiation and formation of memory CD8(+) T cells.
EVALuna2:3800

Updated insight into the mutational and phenotypic spectrum of MED13L-related intellectual disability - Asadollahi, R.; Boonsawat, P.; Popp, B.; Torti, E.; Bader, I.; Vitobello, A.; Moutton, S.; Pinson, L.; Lambert, L.; Thuresson, A. C.; Sobol, M.; Zander, C. Soussi; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Variants in SCAF4 Cause a Neurodevelopmental Disorder and Are Associated with Impaired mRNA Processing - Fliedner, Anna; Kirchner, Philipp; Wiesener, Antje; van de Beek, Irma; Waisfisz, Quinten; van Haelst, Mieke; Scott, Daryl A.; Lalani, Seema R.; Rosenfeld, Jill A.; Azamian, Mahshid S.; Xia, Fan; Dutra-Clarke, Marina; et al. (American Journal of Human Genetics, 2020)
RNA polymerase II interacts with various other complexes and factors to ensure correct initiation, elongation, and termination of mRNA transcription. One of these proteins is SR-related CTD-associated factor 4 (SCAF4), which is important for correct usage of polyA sites for mRNA termination. Using exome sequencing and international matchmaking, we identified nine likely pathogenic germline variants in SCAF4 including two splice-site and seven truncating variants, all residing in the N-terminal two thirds of the protein. Eight of these variants occurred de novo, and one was inherited. Affected individuals demonstrated a variable neurodevelopmental disorder characterized by mild intellectual disability, seizures, behavioral abnormalities, and various skeletal and structural anomalies. Paired-end RNA sequencing on blood lymphocytes of SCAF4-deficient individuals revealed a broad deregulation of more than 9,000 genes and significant differential splicing of more than 2,900 genes, indicating an important role of SCAF4 in mRNA processing. Knockdown of the SCAF4 ortholog CG4266 in the model organism Drosophila melanogaster resulted in impaired locomotor function, learning, and short-term memory. Furthermore, we observed an increased number of active zones in larval neuromuscular junctions, representing large glutamatergic synapses. These observations indicate a role of CG4266 in nervous system development and function and support the implication of SCAF4 in neurodevelopmental phenotypes. In summary, our data show that heterozygous, likely gene-disrupting variants in SCAF4 are causative for a variable neurodevelopmental disorder associated with impaired mRNA processing.
CRIS-Team Scopus Importer:2020-08-21
Keywords: epilepsy; intellectual disability; mRNA processing; neurodevelopmental disorder; SCAF4; seizures

Zeb2 recruits HDAC-NuRD to inhibit Notch and controls Schwann cell differentiation and remyelination - Wu, Lai Man Natalie; Wang, Jincheng; Conidi, Andrea; Zhao, Chuntao; Wang, Haibo; Ford, Zachary; Zhang, Liguo; Zweier, Christiane; Ayee, Brian G.; Maurel, Patrice; Zwijsen, An; Chan, Jonah R.; et al. (Nature Neuroscience, 2016)
The mechanisms that coordinate and balance a complex network of opposing regulators to control Schwann cell (SC) differentiation remain elusive. Here we demonstrate that zinc-finger E-box-binding homeobox 2 (Zeb2, also called Sip1) transcription factor is a critical intrinsic timer that controls the onset of SC differentiation by recruiting histone deacetylases HDAC 1 and 2 (HDAC1/2) and nucleosome remodeling and deacetylase complex (NuRD) co-repressor complexes in mice. Zeb2 deletion arrests SCs at an undifferentiated state during peripheral nerve development and inhibits remyelination after injury. Zeb2 antagonizes inhibitory effectors including Notch and Sox2. Importantly, genome-wide transcriptome analysis reveals a Zeb2 target gene encoding the Notch effector Hey2 as a potent inhibitor for Schwann cell differentiation. Strikingly, a genetic Zeb2 variant associated with Mowat-Wilson syndrome disrupts the interaction with HDAC1/2-NuRD and abolishes Zeb2 activity for SC differentiation. Therefore, Zeb2 controls SC maturation by recruiting HDAC1/2-NuRD complexes and inhibiting a Notch-Hey2 signaling axis, pointing to the critical role of HDAC1/2-NuRD activity in peripheral neuropathies caused by ZEB2 mutations.
EVALuna2:9316